Electromagnetic wave absorbing particle dispersion, electromagnetic wave absorbing laminate, electromagnetic wave absorbing transparent substrate, and method for producing electromagnetic wave absorbing particle dispersion
Cesium tungsten oxide particles with controlled crystal structures address the color neutrality and absorption issues of tungsten oxide-based materials, achieving neutral color tones and improved near-infrared absorption.
Patent Information
- Application Number
- JP2021574123
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-01-28
AI Technical Summary
Existing electromagnetic wave absorbing materials, particularly those using tungsten oxide, exhibit strong blue coloration and limited color neutrality, making them unsuitable for applications requiring neutral or white color tones while maintaining near-infrared absorption.
The use of cesium tungsten oxide particles with specific orthorhombic or hexagonal crystal structures, produced through controlled thermal reduction of cesium tungsten oxide precursors, to achieve a neutral transmitted color tone by adjusting the band gap and electron distribution, thereby reducing solar transmittance.
The solution provides an electromagnetic wave absorbing particle dispersion with a more neutral transmitted color tone and enhanced near-infrared absorption, addressing the limitations of conventional tungsten oxide-based materials.
Smart Images

Figure 0007601013000003 
Figure 0007601013000004 
Figure 0007601013000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave absorbing particle dispersion, an electromagnetic wave absorbing laminate, and an electromagnetic wave absorbing transparent substrate. [Background technology]
[0002] According to the 5th edition of the Physics and Chemistry Dictionary, "Electromagnetic waves with wavelengths in the range of approximately 1 nm to 1 mm are called light." This wavelength range includes the visible light region and the infrared region.
[0003] Near-infrared rays contained in sunlight penetrate windows and other materials, enter indoor spaces, and raise the surface temperatures of the walls and floors inside the rooms, thereby raising the indoor air temperature. In order to make the indoor thermal environment more comfortable, it has been conventional to use light-shielding materials in window materials and other materials to block the near-infrared rays that enter through the windows, thereby preventing the indoor air temperature from rising.
[0004] Patent Document 1 proposes a light-shielding film containing black fine powder including inorganic pigments such as carbon black and titanium black, and organic pigments such as aniline black, as a light-shielding material used in windows and the like.
[0005] Patent Document 2 discloses a thermal insulation sheet made of a woven fabric in which a belt-shaped film having infrared reflectivity and a belt-shaped film having infrared absorbing properties are used as warp and weft, respectively. It also discloses that the belt-shaped film having infrared reflectivity is made by depositing aluminum on a synthetic resin film and further laminating another synthetic resin film.
[0006] The present applicant has proposed in Patent Document 3 an infrared-shielding material microparticle dispersion in which infrared material microparticles are dispersed in a medium, the infrared material microparticles containing tungsten oxide microparticles and / or composite tungsten oxide microparticles, and the dispersed particle diameter of the infrared material microparticles being 1 nm or more and 800 nm or less. [Prior art documents] [Chartered documents]
[0007]
Patent Document 1
Patent document 2
Patent document 3
Non-licensed literature
[0008]
Non-licensed literature 1
Non-licensed Document 2
Non-licensed Document 4
[0009] The above-mentioned Patent Document 3 discloses tungsten oxide particles and / or composite tungsten oxide particles as infrared shielding material particles. A transparent film in which these tungsten oxides are dispersed is colored blue, and the blue color becomes stronger as the amount of the tungsten oxide particles added increases.
[0010] However, in recent years, in applications such as automotive glass and photothermal conversion materials, there has been a demand for a neutral color, i.e., a color without coloring such as blue in the transmitted color, while increasing the near-infrared absorption rate, that is, decreasing the solar transmittance.
[0011] Based on a blue material such as the transmission film in which the above tungsten oxide is dispersed, when the color of the glass is adjusted with various pigments and dyes, the hue obtained is limited. In particular, it is difficult to obtain a yellow-based transmitted color which is a complementary color.
[0012] In addition, in photothermal conversion materials, specifically in applications such as adhesion of transparent resin members by photothermal conversion, a pure white color development is required, but it is difficult to achieve a pure white color development with materials such as the above tungsten oxide.
[0013] On the other hand, for example, regarding a transmission film in which a composite tungsten oxide is dispersed, when the transmitted color is made neutral, that is, a transparent color tone, its applications can be expanded. However, there has been no report so far on a composite tungsten oxide that can realize a neutral color while reducing the solar transmittance when used as a dispersion.
[0014] Therefore, one aspect of the present invention aims to provide an electromagnetic wave absorption particle dispersion having a more neutral color tone in the transmitted color while suppressing the solar transmittance.
Means for Solving the Problems
[0015] In one aspect of the present invention, cesium tungsten oxide represented by the general formula Cs x W 1-y O 3-z (0.2 ≦ x ≦ 0.4, 0 < y ≦ 0.4, 0 < z ≦ 0.46) and having an orthorhombic or hexagonal crystal structure, and an electromagnetic wave absorption particle dispersion including a solid medium, wherein the electromagnetic wave absorption particles are dispersed in the solid medium is provided.
Effects of the Invention
Effects of the Invention
[0016] According to one aspect of the present invention, it is possible to provide an electromagnetic wave absorbing particle dispersion having a more neutral transmitted color while suppressing the solar radiation transmittance. [Brief description of the drawings]
[0017] [Figure 1A] FIG. 1A is an explanatory diagram of the crystal structure of cesium tungsten oxide (Cs4W11O35). [Figure 1B] FIG. 1B is an explanatory diagram of the crystal structure of cesium tungsten oxide (Cs4W12O36). [Figure 2A] FIG. 2A shows the energy band structure of cesium tungsten oxide (Cs4W11O35). [Figure 2B] FIG. 2B is the energy band structure of cesium tungsten oxide (Cs4W12O36). [Figure 2C] FIG. 2C shows the energy band structure of cesium tungsten oxide (Cs4W11O36). [Figure 2D] FIG. 2D shows the energy band structure of cesium tungsten oxide (Cs6W17O54). [Figure 3A] FIG. 3A is the dielectric function of cesium tungsten oxide. [Figure 3B] FIG. 3B is the dielectric function of cesium tungsten oxide. [Figure 4] FIG. 4 is an electron beam diffraction image of the powder A′ obtained in Example 1 taken in the c-axis direction. [Diagram 5] FIG. 5 is an electron beam diffraction image of the
[0001] HEX zone axis of the pseudohexagonal particles of Powder A obtained in Example 1. [Figure 6] FIG. 6 is a STEM-HAADF image of the pseudohexagonal particles of Powder A obtained in Example 1, observed from the
[0221] zone axis. [Figure 7] FIG. 7 is an electron beam diffraction image of the
[0001] HEX zone axis of the pseudohexagonal particles of Powder B obtained in Example 2. [Figure 8]FIG. 8 is an electron beam diffraction image of the
[0001] HEX zone axis of the pseudohexagonal particles of Powder C obtained in Example 3. [Figure 9A] FIG. 9A shows the molar absorption coefficients of the dispersions prepared in Examples 14 to 20 and Comparative Example 1. [Figure 9B] FIG. 9B shows the molar absorption coefficients of the dispersions prepared in Examples 14 to 20 and Comparative Example 1. [Figure 9C] FIG. 9C shows the molar absorption coefficients of the dispersions prepared in Examples 15, 16, 18, 22, and 23, and Comparative Example 1. [Figure 10A] FIG. 10A shows the transmittance profiles of the dispersions prepared in Example 15, Example 16, Example 19, and Comparative Examples 1 to 3, which were derived so as to maintain a constant VLT. [Figure 10B] FIG. 10B shows the transmittance profiles of the dispersions prepared in Example 15, Example 16, Example 19, and Comparative Examples 1 to 3, which were derived so as to maintain a constant VLT. [Figure 11A] FIG. 11A is an explanatory diagram showing the change with reduction time in the near-infrared absorption characteristics of the dispersions according to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19. [Figure 11B] FIG. 11B is an explanatory diagram of the change in color index of the dispersion liquids according to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19 with the reduction time. [Figure 11C] FIG. 11C is an explanatory diagram of the change in color index of the dispersion liquids according to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19 with the reduction time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention. [Electromagnetic wave absorbing particles and method for producing the electromagnetic wave absorbing particles] Before describing the electromagnetic wave absorbing particle dispersion of this embodiment, electromagnetic wave absorbing particles and a method for producing the electromagnetic wave absorbing particles that can be suitably used in the electromagnetic wave absorbing particle dispersion of this embodiment will be described. (1) Electromagnetic wave absorbing particles The transmission color of cesium-doped hexagonal tungsten bronze nanoparticles, which have been used as electromagnetic wave absorbing particles, is determined by the imaginary part of its dielectric function (ε 2 )(The experimentally obtained ε 2 is given in Non-Patent Document 1) and the band structure (Non-Patent Document 2).
[0019] In the visible light energy range (1.6 eV to 3.3 eV), cesium-doped hexagonal tungsten bronze (hereafter referred to as Cs-HTB) has a sufficiently large band gap. In addition, the probability of electronic transitions between dd orbitals of tungsten is small because the Fermi golden rule prohibits such transitions, and the ε 2 takes a small value. ε 2 represents the absorption of a photon by an electron, so ε 2 If is small at visible wavelengths, visible light transmittance occurs. However, in the vicinity of blue wavelengths, which have the shortest wavelengths in the visible light region, absorption due to interband transitions occurs, and in the vicinity of red wavelengths, which have the longest wavelengths, localized surface plasmon resonance (LSPR) absorption and polaronic electronic transition absorption occur (Non-Patent Document 3). For these reasons, light transmittance is restricted in each case.
[0020] As mentioned above, the band gap of Cs-HTB is large enough that the interband transition exceeds the energy of blue wavelength light, resulting in high blue transmittance. Conversely, on the red wavelength side, Cs-HTB has many conduction electrons, so LSPR absorption and polaronic absorption become stronger, and at the same time, the absorption wavelength approaches the red wavelength side, resulting in low transmittance. Therefore, the transmitted color of the Cs-HTB nanoparticle dispersion film appears blue.
[0021] In other words, in order to neutralize the blue transmission color of Cs-HTB, it is necessary to strengthen the absorption on the blue side and the transmission on the red side. To achieve this, it is preferable to shift the absorption position of the interband transition to lower energy and to weaken the LSPR absorption and polaronic absorption and shift them to the lower energy side.
[0022] In order to weaken the LSPR absorption or polaronic absorption, it is effective to reduce the amount of free electrons and bound electrons contained in the material.
[0023] The increase in blue absorption is achieved by using materials with different energy band structures that have a lower energy band gap. The transmission in the red is achieved by using cesium ions (Cs + ) and oxygen vacancies (V O ) can be controlled by increasing or decreasing the amount.
[0024] Based on the above considerations, the inventors of the present invention have conducted various studies on cesium tungsten oxide, which is an oxide containing cesium (Cs) and tungsten (W), and have found that a cesium tungsten oxide precursor containing Cs and W, nCs 2 O·mWO 3 It was discovered that when electromagnetic wave absorbing particles containing cesium tungsten oxide obtained by reducing a crystal powder of (n, m are integers, 3.6≦m / n≦9.0) are used, the color tone of the transparent film, which is an electromagnetic wave absorbing particle dispersion, also becomes less blue and becomes neutral.
[0025] The electromagnetic wave absorbing particles are made by reducing a compound with a narrower band gap than hexagonal Cs-HTB and a lower blue transmittance. O It is believed that the color tone was neutralized by gradually increasing the LSPR absorption and polaronic absorption within the allowable range and optimizing the red transmittance.
[0026] The above cesium tungsten oxide precursor containing Cs nCs 2 O·mWO 3In the electronegative element, Cs and W, the charges are neutralized by O, making them non-conductors. Cs 2 W 7 O 22 , Cs 6 W 20 O 63 , Cs 2 W 6 O 19 , Cs 4 W 11 O 35 , Cs 6 W 11 O 36 , Cs 2 W 3 O 10 etc. 3 -Cs 2 In compounds along the O line, the valences are balanced, so the Fermi energy E F exists between the valence band and the conduction band, and is a non-conductor. When the Cs / W ratio (molar ratio) is 0.2 or more, in order to incorporate Cs, which has a large ionic radius, the basic framework formed by the WO octahedron is either a hexagonally symmetric structure with large hexagonal gaps, or a crystal structure in which the atomic arrangement of a hexagonal or cubic crystal (pyrochlore structure) with large hexagonal gaps has planar defects including W vacancies (tungsten vacancies) and the symmetry is reduced to an orthorhombic or monoclinic crystal.
[0027] For example, 2Cs 2 O·11WO 3 In the model of Solodovnikov 1998 (Non-Patent Document 4), in the hexagonal arrangement of WO octahedra similar to hexagonal tungsten bronze, faces with missing W and O are inserted at a pitch of b / 8 of the orthorhombic unit cell on the hexagonal (110) face (=orthorhombic (010) face), forming an orthorhombic crystal as a whole. 2 O·mWO 3(n, m are integers, 3.6≦m / n≦9.0) has a narrower band gap than Cs-HTB, and therefore has low blue transmittance. However, when this is heated and reduced, the whole gradually changes to the hexagonal crystal structure of tungsten bronze, and in the process, the band structure changes, the band gap widens, and the absorption of blue light becomes weaker, resulting in stronger blue transmittance. In addition, as the reduction progresses, electrons are gradually injected into the conduction band, turning the material into a conductor, and the band gap gradually widens due to the Burstein-Moss effect, further enhancing blue transmittance.
[0028] When the orthorhombic crystals are converted to hexagonal crystals by heating and reduction, the planar defects including W vacancies in the orthorhombic crystals gradually disappear, and a hexagonal crystal framework of WO octahedra is formed. The planar defects including W vacancies are (010) ORTH The surface is a hexagonal prism {100} HEX , i.e. [(100) HEX ,(010) HEX ,(110) HEX ], so as the material is heated and reduced, HEX The hexagonal crystals have defects on the faces. HEX Due to the defects in the faces, the crystal structure is not perfect hexagonal symmetry and can be said to be pseudo-hexagonal. In this way, the crystal structure changes from orthorhombic to pseudo-hexagonal and then to hexagonal with heating and reduction. At this time, the (010) ORTH The planar defects on the surface are {100} HEX It is believed that this is inherited by the surface defects on the surface, gradually decreasing and eventually disappearing.
[0029] The electronic structure also changes as the crystal structure changes during heating and reduction. The disappearance of W vacancies results in the injection of a large amount of electrons into the material. In the orthorhombic crystal, the outer shell electrons of Cs are used to neutralize O, resulting in an overall charge neutrality. However, when the W vacancies are reduced and the crystal becomes pseudohexagonal, six outer shell electrons per W atom are used to neutralize O, and the outer shell electrons of Cs enter the W-5d orbital below the conduction band and become free electrons. These free electrons absorb near-infrared light due to LSPR absorption. On the other hand, heating and reduction simultaneously increases the amount of V OIt has the effect of generating V O The generation of proceeds at random sites. V O When this occurs, the W atoms on both sides become overcharged, and W 5+ Localized electrons bound to the orbital are generated (Non-Patent Document 2). These localized electrons transition to vacancies in the upper part of the conduction band, resulting in polaronic absorption, but some of them are excited to free electron orbitals, resulting in LSPR absorption (Non-Patent Document 3). The absorption by these free electrons and bound electrons both has a peak wavelength in the near infrared, so the base of the absorption falls on the red wavelength, thus reducing the transmittance of red light. The greater the amount of free electrons and bound electrons, i.e., the greater the degree of reduction, the more the LSPR absorption and polaronic absorption wavelengths shift to higher wavelengths and the greater the amount of absorption, so the transmittance of red light decreases.
[0030] Therefore, the cesium tungsten oxide precursor nCs 2 O·mWO 3 (n, m are integers, 3.6≦m / n≦9.0) crystal powder is reduced and the degree of reduction is adjusted to neutralize the blue-based transmitted color.
[0031] The electromagnetic wave absorbing particles that can be suitably used in the electromagnetic wave absorbing particle dispersion of the present embodiment described above are cesium tungsten oxide precursors containing Cs and W, 2 O·mWO 3 It can be produced by heating the crystal powder of the above in a reducing atmosphere at 650° C. to 950° C. In the formula of the cesium tungsten oxide, n and m are integers, and preferably satisfy 3.6≦m / n≦9.0.
[0032] That is, the electromagnetic wave absorbing particles are cesium tungsten oxide precursors containing cesium and tungsten (nCs). 2 O·mWO 3 Particles obtained by heating and reducing a crystal powder of (n, m are integers, 3.6≦m / n≦9.0) in a reducing gas atmosphere at 650° C. to 950° C. can be used.
[0033] In order for all or part of the material to become hexagonal tungsten bronze by heating and reduction, the m / n value must be in the range of 3.6≦m / n≦9.0 as mentioned above. If it is less than 3.6, the material will become a cubic pyrochlore phase after heating and reduction, which will cause strong coloring and no near-infrared absorption. If it is more than 9.0, the material will separate into hexagonal tungsten bronze and tungsten trioxide after heating and reduction, and the near-infrared absorption effect will be significantly reduced. The above cesium tungsten oxide precursor is Cs, with m / n=5.5. 4 W 11 O 35 It is more preferable that the electromagnetic wave absorbing particles are Cs 4 W 11 O 35 It is more preferable to use particles obtained by heating and reducing a cesium tungsten oxide precursor containing the Cs phase in a reducing gas atmosphere at a temperature of 650°C to 950°C. 4 W 11 O 35 By forming an electromagnetic wave absorbing particle dispersion using the electromagnetic wave absorbing particles obtained by high-temperature reduction of the above, it is possible to obtain a large near-infrared absorbing effect while having a transmitted color with a suppressed blue tint. Note that the main phase referred to here means the phase that is contained in the largest amount by mass ratio.
[0034] As mentioned above, the heating temperature during reduction of cesium tungsten oxide is preferably 650°C or higher and 950°C or lower. By setting the temperature at 650°C or higher, the structural change from orthorhombic to hexagonal can be sufficiently promoted, and the near-infrared absorption effect can be enhanced. In addition, by setting the temperature at 950°C or lower, the speed of the crystal structure change can be appropriately maintained, and it is possible to easily control the crystal state and electronic state to an appropriate state. However, if the heating temperature is higher than 950°C and reduction proceeds too far, W metal and WO 2 In some cases, lower oxides such as those mentioned above may be produced, which is undesirable from this viewpoint as well.
[0035] The electromagnetic wave absorbing particles that can be suitably used in the electromagnetic wave absorbing particle dispersion of this embodiment are represented by the general formula Cs x W 1-y O 3-zIt can contain cesium tungstate having an orthorhombic or hexagonal crystal structure, represented by (0.2 ≦ x ≦ 0.4, 0 < y ≦ 0.4, 0 < z ≦ 0.46).
[0036] When the cesium tungstate contained in the electromagnetic wave absorbing particles satisfies the above general formula, the degree of W deficiency and oxygen vacancies Vo is in an appropriate range. When it is made into an electromagnetic wave absorbing particle dispersion, it is possible to obtain an electromagnetic wave absorbing particle dispersion that suppresses the solar transmittance while having a more neutral color tone of the transmitted color.
[0037] Note that the electromagnetic wave absorbing particles can also be composed of the above composite tungstate. However, even in this case, it does not exclude containing inevitable impurities mixed in during the manufacturing process or the like.
[0038] Conventionally known tungsten bronzes for electromagnetic wave absorption have a hexagonal crystal structure. On the other hand, the composite tungstate of the electromagnetic wave absorbing particles used in the electromagnetic wave absorbing particle dispersion of the present embodiment can have an orthorhombic or hexagonal crystal structure. Here, the hexagonal crystal includes pseudo-hexagonal crystals.
[0039] The composite tungstate contained in the electromagnetic wave absorbing particles preferably has linear or planar defects on one or more surfaces selected from the (010) plane of the orthorhombic crystal, the {100} plane which is the prism plane of the hexagonal crystal, and the (001) plane which is the bottom plane of the hexagonal crystal. The above defects include stacking irregularities based on the displacement between planes, and disorders in the arrangement and atomic positions of Cs atoms and W atoms within the plane. Therefore, the electron diffraction spots often have streaks. The {100} plane which is the prism plane of the hexagonal crystal means the (100) plane, the (010) plane, and the (110) plane. Such defects of the composite tungstate, that is, lattice defects, involve at least W deficiency, specifically, partial deficiency of W. This W deficiency causes the lack of electrons in the crystal, and as described above, this is one of the essential causes and acts on the neutralization of the blue color tone.
[0040] Cesium tungsten oxide has defects, which can include tungsten vacancies as discussed above.
[0041] In addition, some of the O atoms in the WO octahedrons that make up the orthorhombic or hexagonal crystals that form the basic structure of cesium tungsten oxide can be randomly lost. O is introduced randomly as described above, and is the same as the known hexagonal tungsten bronze Cs 0.32 WO 3-y It is known that in the case of y=0.46 or O, the ratio of the total lattice points reaches a maximum of 15% (Non-Patent Document 5). x W 1-y O 3-z At z=0.46, the maximum amount of V O That is, z may be less than or equal to 0.46.
[0042] The lattice constant of the cesium tungsten oxide corresponds to the amount of defects in the crystal lattice, or the composition, and the crystallinity. The a-axis value varies with these variables, but the c-axis value corresponds relatively well to the amount of lattice defects or the optical properties. As a result, the cesium tungsten oxide contained in the electromagnetic wave absorbing particles used in the electromagnetic wave absorbing particle dispersion of this embodiment preferably has a c-axis length in hexagonal crystal conversion of 7.560 Å or more and 7.750 Å or less. By setting the c-axis length in hexagonal crystal conversion of the cesium tungsten oxide within the above range, the near-infrared absorption effect can be sufficiently improved, and the visible light transmittance can be particularly improved. Note that when the cesium tungsten oxide is a hexagonal crystal, conversion is not necessary, and the c-axis length in the hexagonal crystal becomes the c-axis length in hexagonal crystal conversion.
[0043] The cesium tungsten oxide contained in the electromagnetic wave absorbing particles used in the electromagnetic wave absorbing particle dispersion of this embodiment is often identified as a mixed phase of orthorhombic and hexagonal crystals when the diffraction pattern of the sample is measured by X-ray powder diffraction method. For example, Cs 4 W 11 O 35By reducing the raw material, orthorhombic Cs 4 W 11 O 35 and hexagonal Cs 0.32 WO 3 In this case, the lattice constants of each phase can be obtained by Rietveld analysis or the like, and these can be converted into hexagonal equivalent values. As already explained, the orthorhombic crystal is a hexagonal crystal with lattice defect planes, so the lattice constants of the orthorhombic crystal can be converted into the lattice constants of the hexagonal crystal by using an appropriate lattice correspondence model. If we assume that the correspondence of the lattice changes between the orthorhombic crystal and the hexagonal crystal is the model of Solodovnikov 1998 (Non-Patent Document 4), then from the geometric relationship to this model, 4a orth 2 +b orth 2 =64a hex 2 = 64b hex 2 , c orth =c hex The relationship between the above can be extracted, and by using these equations, the lattice constants can be calculated in terms of hexagonal crystals. orth , b orth , c orth means the length of the a-axis, b-axis, and c-axis of the orthorhombic crystal. hex , b hex , c hex means the lengths of the a-axis, b-axis, and c-axis of the hexagonal crystal.
[0044] The cesium tungsten oxide contained in the electromagnetic wave absorbing particles used in the electromagnetic wave absorbing particle dispersion of this embodiment may have a part of Cs replaced with an additive element, in which case the additive element is preferably one or more selected from the group consisting of Na, Tl, In, Li, Be, Mg, Ca, Sr, Ba, Al, and Ga.
[0045] These added elements have electron donating properties and assist in donating electrons to the conduction band of the WO octahedral framework at the Cs site.
[0046] The average particle size of the electromagnetic wave absorbing particles of this embodiment is not particularly limited, but is preferably 0.1 nm or more and 200 nm or less. This is because by making the average particle size of the electromagnetic wave absorbing particles 200 nm or less, the localized surface plasmon resonance is more significantly expressed, so that the near-infrared absorption characteristics can be particularly improved, that is, the solar radiation transmittance can be particularly suppressed. In addition, by making the average particle size of the electromagnetic wave absorbing particles 0.1 nm or more, it is easy to manufacture industrially. In addition, the particle size is closely related to the color of the dispersion transmission film, that is, the electromagnetic wave absorbing particle dispersion, and in the particle size range where Mie scattering is dominant, the smaller the particle size, the less scattering of short wavelengths in the visible light region. Therefore, increasing the particle size has the effect of suppressing the blue tone, but if it exceeds 100 nm, the haze of the film due to light scattering becomes large enough to be ignored, and if it exceeds 200 nm, in addition to the increase in the haze of the film, the generation of surface plasmons is suppressed, and the LSPR absorption becomes excessively small.
[0047] Here, the average particle size of the electromagnetic wave absorbing particles can be known from the median size of a plurality of electromagnetic wave absorbing particles measured from a transmission electron microscope image, or from the dispersed particle size measured by a particle size measuring device based on the dynamic light scattering method of the dispersion liquid.
[0048] In addition, when the electromagnetic wave absorbing particles are used in applications where transparency in the visible light region is particularly important, such as automobile windshields, it is preferable to further consider the reduction in scattering caused by the electromagnetic wave absorbing particles. In cases where the reduction in scattering is important, it is particularly preferable that the average particle size of the electromagnetic wave absorbing particles is 30 nm or less.
[0049] The average particle size means the particle size at 50% of the cumulative value in the particle size distribution, and the average particle size has the same meaning in other parts of this specification. As a method for measuring the particle size distribution to calculate the average particle size, for example, a direct measurement of the particle size of each particle can be used using a transmission electron microscope. In addition, the average particle size can also be measured by a particle size measuring device based on the dynamic light scattering method of the dispersion liquid as described above.
[0050] The electromagnetic wave absorbing particles may also be surface-treated for the purposes of surface protection, improving durability, preventing oxidation, improving water resistance, etc. The specific content of the surface treatment is not particularly limited, but for example, the electromagnetic wave absorbing particles of this embodiment may have their surfaces modified with a compound containing one or more types of atoms selected from Si, Ti, Zr, and Al. In this case, examples of the compound containing one or more types of atoms (elements) selected from Si, Ti, Zr, and Al include one or more types selected from oxides, nitrides, carbides, etc.
[0051] Here, the band structures of cesium tungsten oxide and cesium tungsten oxide precursor will be described.
[0052] As explained above, nCs 2 O·mWO 3 (n, m are integers, 3.6≦m / n≦9.0) was reduced at high temperatures to obtain a solar radiation shading material with a more neutral transparent color. O It is believed that the generation of this compound injects electrons into the conduction band, which is the source of near-infrared absorption. This change in electronic structure is supported by first-principles calculations.
[0053] Figure 1A shows Cs 4 W 11 O 35 The crystal structure of Cs is shown in Fig. 1B. 0.33 WO 3 Cs 4 W 12 O 36 The crystal structure of Cs is shown in Fig. 1A and Fig. 1B. Cesium-11 and oxygen-12 are shown. Atoms of the same type are hatched with the same pattern. Tungsten is not shown in Fig. 1A and Fig. 1B because it is arranged in an octahedron formed by oxygen-12. Fig. 1B shows the crystal structure of Cs 0.33 WO 3 , Cs in Figure 1A 4 W 11 O 35 It is an orthorhombic structure with its axis reoriented so that it can be compared with the above.
[0054] Cs in Figure 1A 4 W 11 O 35 The structure of Cs in Figure 1B 4 W 12 O 36 In the crystal structure, W and O are regularly deficient.
[0055] The band structures of the cesium tungsten oxides having the crystal structures shown in Figures 1A and 1B are shown in Figures 2A and 2B, respectively. 4 W 12 O 36 Based on this, Cs with one missing W 4 W 11 O 36 The band structure of Cs with one missing W atom, and the cell size of Cs is 1.5 times larger in the b-axis direction. 6 W 17 O 54 The band structures of these are shown in Figures 2C and 2D, respectively.
[0056] Cs shown in Fig. 2A and Fig. 2B 4 W 11 O 35 The band structure of Cs 4 W 12 O 36 The band structures are similar, but the Fermi energy (E F ) is located inside the band gap in the former case and below the conduction band in the latter case. 4 W 11 O 35 is an insulator, and Cs 4 W 12 O 36 is an electrical conductor. Cs 4 W 11 O 35 So, Cs 4 W 12 O 36 Based on the standard, there is one W and one O missing in the unit cell. 4 W 12 O 36 So, hexagonal WO 3 It is interpreted that a network of these is formed, and Cs electrons are injected into the W-5d orbital to make the material conductive (Non-Patent Document 6).
[0057] Cs in Figure 2C 4 W 11 O 36 is Cs in Figure 2B 4 W 12 O 36 This structure has one W subtracted from the above.
[0058] Cs in Fig. 2D 6 W 17 O 54 , i.e. 3Cs 2 O·17WO 3 is Cs in Figure 2B 4 W 12 O 36 , i.e. Cs 6 W 18 O 54 From this perspective, the structure has one W removed while maintaining charge neutrality.
[0059] The amount of W defect decreases in the order of Figure 2A, Figure 2D, and Figure 2B, but E F rises toward the bottom side of the conductor, which confirms that W electrons are injected into the W-5d orbital, increasing the number of conduction electrons and increasing the near-infrared absorption. Cs 4 W 12 O 36 Detailed calculation examples have already been reported for the case where O is deficient in the conduction band, and it has been found that localized orbitals are introduced at the bottom of the conduction band and the number of free electrons and localized electrons increases significantly (Non-Patent Document 2).
[0060] In the experimentally obtained pseudo-hexagonal crystal (an intermediate structure in the middle of the phase transition between orthorhombic and hexagonal crystals), the electronic state is considered to be a mixture of the above elements. In other words, with reduction, hexagonal crystallization including the disappearance of W vacancies and V O As a result of this generation, electrons are gradually injected into the conduction band, and the Fermi energy E F rises from the band gap to the bottom of the conduction band.
[0061] Based on these band structures, the dielectric function including the Drude term was calculated and the results are shown in Fig. 3A and Fig. 3B. The dielectric function ε 1 ε1 If we focus on the position of Ω = 0, the shielded plasma frequency (Ω SP ) is Cs 4 W 11 O 35 , Cs 6 W 17 O 54 , Cs 4 W 12 O 36 , Cs 4 W 12 O 35 It can be seen that the near-infrared absorption increases in this order. It is expected that the near-infrared absorption increases in this order, and this tendency coincides with the observed results.
[0062] The dielectric function ε shown in Fig. 3A 2 From the plot, cesium tungsten oxide has a ε 2 In the blue region of 3.3 eV indicated by the dotted line 31, the band gap is narrow due to the band-to-band transition. 4 W 11 O 35 Or Cs 6 W 17 O 54 On the other hand, at 1.6 eV in the red region shown by the dotted line 32, the absorption of Cs 4 W 12 O 35 The absorption of Ω is large in the red region. SP It is expected that the ε 2 The profile of Fig. 9B basically corresponds to the experimentally observed profile of Fig. 9B, and the tendency is well reproduced. That is, the reason why the blueness is reduced in the cesium tungsten oxide contained in the electromagnetic wave absorbing particles that can be suitably used in the electromagnetic wave absorbing particle dispersion of this embodiment, compared with the cesium tungsten oxide that has been conventionally used, is that the cesium tungsten oxide has a vacancy of W and O. 2 O·mWO 3 By using (3.6≦m / n≦9.0) as the raw material, Cs containing W deficiency was obtained. 0.33 W 1-y O 3―zThis is thought to be due to the formation of a phase, which increases the absorption on the high energy side. 2 O·mWO 3 By adjusting the high-temperature reduction of (3.6≦m / n≦9.0), the band gap and the amount of electrons injected into the conduction band can be adjusted, and the bluish color tone can be adjusted. It was also confirmed that the near-infrared absorption effect at that time remains relatively high. (Method of manufacturing electromagnetic wave absorbing particles) The method for producing the electromagnetic wave absorbing particles described above is not particularly limited, and any method can be used as long as it can produce electromagnetic wave absorbing particles that satisfy the above-mentioned characteristics. Here, one configuration example of the method for producing the electromagnetic wave absorbing particles will be described.
[0063] A method for producing electromagnetic wave absorbing particles can include, for example, the following steps.
[0064] A cesium tungsten oxide precursor synthesis step of synthesizing a cesium tungsten oxide precursor, which is a tungstate salt containing cesium. A heating and reduction process in which the cesium tungsten oxide precursor is heated and reduced at 650°C to 950°C in a reducing gas atmosphere.
[0065] Each step will be described below. (1) Cesium tungsten oxide precursor synthesis process In the cesium tungsten oxide precursor synthesis step, a tungstate containing cesium, i.e., a cesium tungstate precursor that is a cesium tungstate, can be synthesized. When the cesium tungsten oxide precursor has already been synthesized, the method for producing the electromagnetic wave absorbing particles of this embodiment can also start with a heating reduction step.
[0066] The precursor of cesium tungsten oxide, which is cesium tungstate, is nCs 2 O·mWO 3(n, m are integers, 3.6≦m / n≦9.0) is preferable. As the cesium tungsten oxide precursor, which is cesium tungstate, it is more preferable to use a stable cesium tungstate. As a stable cesium tungstate, Cs 4 W 11 O 35 , Cs 2 W 6 O 19 , Cs 6 W 20 O 63 , Cs 2 W 7 O 22 , Cs 6 W 11 O 36 The cesium tungsten oxide precursor is particularly preferably Cs as the main phase. 4 W 11 O 35 More preferably, it is a cesium tungsten oxide precursor containing a phase.
[0067] These cesium tungstates can be prepared, for example, by firing a raw material powder mixture containing cesium and tungsten in air at 700° C. to 1000° C. The method for producing cesium tungstate is not limited to the above-mentioned form, and other methods such as a sol-gel method or a complex polymerization method can also be used.
[0068] Furthermore, as the cesium tungstate used as the starting material, a non-equilibrium tungstate obtained by gas phase synthesis or the like may be used. This includes powder obtained by a thermal plasma method and powder obtained by electron beam melting. (2) Heat reduction process The above-mentioned cesium tungsten oxide precursor as a starting material, specifically, for example, cesium tungstate having one or more crystal structures selected from orthorhombic, monoclinic, and pseudohexagonal, can be subjected to a heating and reduction step.
[0069] In the heating and reducing step, the above-mentioned cesium tungsten oxide precursor can be heated and reduced in a reducing gas atmosphere at 650° C. to 950° C. By carrying out the heating and reducing step, electromagnetic wave absorbing particles containing cesium tungsten oxide of a desired composition can be obtained.
[0070] When the heat reduction treatment is performed, it is preferable to perform the treatment under a flow of a reducing gas. As the reducing gas, a mixed gas containing a reducing gas such as hydrogen and one or more inert gases selected from nitrogen, argon, etc. may be used. In addition, heating in a water vapor atmosphere or a vacuum atmosphere or other mild heating and reduction conditions may be used in combination.
[0071] The method for producing the electromagnetic wave absorbing particles of this embodiment is not particularly limited to the above-mentioned embodiment. As the method for producing the electromagnetic wave absorbing particles, various methods that can form a predetermined structure including a defective microstructure can be used. The method for producing the electromagnetic wave absorbing particles includes a method for reducing a tungstate obtained by a solid-phase method, a liquid-phase method, or a gas-phase method, and a method for reducing WO in a molten alkali halide. 3 Examples of the method include a method for reducing the amount of
[0072] The method for producing the electromagnetic wave absorbing particles may further include any optional steps. (3) Crushing process As described above, the electromagnetic wave absorbing particles are preferably finely divided into fine particles, and therefore the method for producing the electromagnetic wave absorbing particles may include a pulverization step of pulverizing the powder obtained in the heating and reducing step.
[0073] The specific means for pulverizing and finely pulverizing is not particularly limited, and various means capable of mechanically pulverizing can be used. As a mechanical pulverizing method, a dry pulverizing method using a jet mill or the like can be used. Moreover, mechanical pulverization may be performed in a solvent in the process of obtaining an electromagnetic wave absorbing particle dispersion liquid described later. (4) Modification process As described above, the surface of the electromagnetic wave absorbing particle may be modified with a compound containing one or more atoms selected from Si, Ti, Zr, and Al. Therefore, the method for producing the electromagnetic wave absorbing particle may further include, for example, a modification step of modifying the electromagnetic wave absorbing particle with a compound containing one or more atoms selected from Si, Ti, Zr, and Al.
[0074] In the modification step, the specific conditions for modifying the electromagnetic wave absorbing particles are not particularly limited. For example, the modification step may include a step of adding an alkoxide or the like containing one or more atoms selected from the above atomic group (metallic group) to the electromagnetic wave absorbing particles to be modified, and forming a coating on the surface of the electromagnetic wave absorbing particles. [Electromagnetic wave absorbing particle dispersion] Next, a configuration example of the electromagnetic wave absorbing particle dispersion liquid of this embodiment will be described.
[0075] The electromagnetic wave absorbing particle dispersion of this embodiment can contain the electromagnetic wave absorbing particles described above and one or more liquid media selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers. The electromagnetic wave absorbing particle dispersion preferably has a configuration in which the electromagnetic wave absorbing particles are dispersed in the liquid medium.
[0076] As described above, the liquid medium may be one or more selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers.
[0077] As the organic solvent, various solvents such as alcohols, ketones, hydrocarbons, glycols, and water-based solvents can be selected. Specifically, alcohol solvents such as isopropyl alcohol, methanol, ethanol, 1-propanol, isopropyl alcohol, butanol, pentanol, benzyl alcohol, diacetone alcohol, and 1-methoxy-2-propanol; ketone solvents such as dimethyl ketone, acetone, methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; ester solvents such as 3-methyl-methoxy-propionate and butyl acetate; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethyl ether, and ethyl ether. Examples of the alkyl group include one or more selected from the group consisting of glycol derivatives such as propylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, and N-methyl-2-propylidone; aromatic hydrocarbons such as toluene and xylene; and halogenated hydrocarbons such as ethylene chloride and chlorobenzene.
[0078] However, among these, organic solvents with low polarity are preferred, and in particular, isopropyl alcohol, ethanol, 1-methoxy-2-propanol, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, etc. These organic solvents can be used alone or in combination of two or more kinds.
[0079] Examples of fats and oils that can be used include one or more selected from drying oils such as linseed oil, sunflower oil, and tung oil; semi-drying oils such as sesame oil, cottonseed oil, rapeseed oil, soybean oil, and rice bran oil; non-drying oils such as olive oil, coconut oil, palm oil, and dehydrated castor oil; fatty acid monoesters obtained by directly esterifying fatty acids of vegetable oils with monoalcohols; ethers; and petroleum-based solvents such as Isopar (registered trademark) E, Exxor (registered trademark) Hexane, Heptane, E, D30, D40, D60, D80, D95, D110, and D130 (all manufactured by ExxonMobil).
[0080] As the liquid resin, for example, one or more types selected from liquid acrylic resin, liquid epoxy resin, liquid polyester resin, liquid urethane resin, and the like can be used.
[0081] As the liquid plasticizer, for example, a liquid plasticizer for plastics can be used.
[0082] The components contained in the electromagnetic wave absorbing particle dispersion are not limited to the electromagnetic wave absorbing particles and the liquid medium described above. The electromagnetic wave absorbing particle dispersion may further contain any optional components added thereto, if necessary.
[0083] For example, an acid or an alkali may be added to the electromagnetic wave absorbing particle dispersion liquid as necessary to adjust the pH of the dispersion liquid.
[0084] In order to further improve the dispersion stability of the electromagnetic wave absorbing particles in the above-mentioned electromagnetic wave absorbing particle dispersion and to prevent the dispersed particle size from becoming coarse due to re-aggregation, various types of surfactants, coupling agents, etc. can also be added to the electromagnetic wave absorbing particle dispersion as dispersants.
[0085] The dispersant such as the surfactant or coupling agent can be selected according to the application, but it is preferable that the dispersant has one or more functional groups selected from an amine-containing group, a hydroxyl group, a carboxyl group, and an epoxy group. These functional groups adsorb to the surface of the electromagnetic wave absorbing particles to prevent aggregation, and have the effect of dispersing the electromagnetic wave absorbing particles uniformly even in the infrared shielding film formed using the electromagnetic wave absorbing particles. A polymer dispersant having one or more functional groups selected from the above functional groups (functional groups) in the molecule is more preferable.
[0086] Suitable commercially available dispersants include Solsperse (registered trademark) 9000, 12000, 17000, 20000, 21000, 24000, 26000, 27000, 28000, 32000, 35100, 54000, and 250 (manufactured by Lubrizol Japan Co., Ltd.), and EFKA (registered trademark). 4008, 4009, 4010, 4015, 4046, 4047, 4060, 4080, 7462, 4020, 4050, 4055, 4400, 4401, 4402, 4403, 4300, 4320, 4330, 4340, 6220, 6225, 6700, 6780, 6782, 8503 (manufactured by Fuka Additives), AJISPER (registered trademark) PA111, PB821, PB822, PN411, Famex L-12 (manufactured by Mai-no-moto Fine Techno Co., Ltd.), DisperBYK (registered trademark) 101, 102, 106, 108, 111, 116, 130, 140, 142, 145, 161, 162, 163, 164, 166, 167, 168, 170, 171, 174, 180, 182, 192, 193, 2000, 2001, 2020, 2025, 2050, 2070, 2155, 2164, 220S, 300, 306, 320, 322, 325, 330, 340, 350, 377, 378, 380N, 410, 425, 430 (manufactured by Pick Chemi-Japan Co., Ltd.), Disparon (registered trademark) Examples of the suitable polyimide resin include one or more selected from the group consisting of 1751N, 1831, 1850, 1860, 1934, DA-400N, DA-703-50, DA-725, DA-705, DA-7301, DN-900, NS-5210, and NVI-8514L (manufactured by Kusumoto Chemicals Co., Ltd.), Arfon (registered trademark) UC-3000, UF-5022, UG-4010, UG-4035, and UG-4070 (manufactured by Toagosei Co., Ltd.).
[0087] The method for dispersing the electromagnetic wave absorbing particles in the liquid medium is not particularly limited as long as the method can disperse the electromagnetic wave absorbing particles in the liquid medium. In this case, it is preferable that the electromagnetic wave absorbing particles are dispersed so that the average particle size is 200 nm or less, and more preferably, the average particle size is 0.1 nm or more and 200 nm or less.
[0088] Examples of the dispersion method of the electromagnetic wave absorbing particles in a liquid medium include dispersion methods using devices such as a bead mill, a ball mill, a sand mill, a paint shaker, and an ultrasonic homogenizer. Among them, it is preferable to pulverize and disperse the particles using a media agitation mill such as a bead mill, a ball mill, a sand mill, or a paint shaker that uses a media (beads, balls, Ottawa sand) from the viewpoint of shortening the time required to obtain a desired average particle size. By the pulverization-dispersion treatment using a media agitation mill, the electromagnetic wave absorbing particles are dispersed in a liquid medium, and at the same time, the particles are atomized due to collisions between the electromagnetic wave absorbing particles and collisions of the media with the electromagnetic wave absorbing particles, and the electromagnetic wave absorbing particles can be dispersed in a more atomized form. That is, the particles are pulverized-dispersed.
[0089] The average particle size of the electromagnetic wave absorbing particles is preferably 0.1 nm or more and 200 nm or less as described above. This is because, if the average particle size is small, scattering of light in the visible light region with a wavelength of 400 nm or more and 780 nm or less due to geometric scattering or Mie scattering is reduced, and as a result, for example, the electromagnetic wave absorbing particle dispersion obtained by using the electromagnetic wave absorbing particle dispersion liquid of this embodiment in which the electromagnetic wave absorbing particles are dispersed in a resin or the like becomes like cloudy glass, and it is possible to avoid the fact that clear transparency cannot be obtained. That is, when the average particle size is 200 nm or less, the light scattering becomes weak in the geometric scattering or Mie scattering mode and becomes a Rayleigh scattering mode. In the Rayleigh scattering region, the scattered light is proportional to the sixth power of the dispersed particle size, so that the scattering is reduced and the transparency is improved as the dispersed particle size decreases. And, when the average particle size is 100 nm or less, the scattered light is very small, which is preferable.
[0090] Incidentally, the dispersion state of the electromagnetic wave absorbing particles in the electromagnetic wave absorbing particle dispersion obtained by using the electromagnetic wave absorbing particle dispersion of this embodiment, in which the electromagnetic wave absorbing particles are dispersed in a solid medium such as a resin, does not result in aggregation below the average particle size of the electromagnetic wave absorbing particles in the dispersion, so long as a known method for adding the dispersion to the solid medium is used.
[0091] In addition, if the average particle diameter of the electromagnetic wave absorbing particles is 0.1 nm or more and 200 nm or less, it is possible to avoid the electromagnetic wave absorbing particle dispersion and its molded body (such as a plate or a sheet) produced from becoming a grayish one with a monotonically decreasing transmittance.
[0092] The content of the electromagnetic wave absorbing particles in the electromagnetic wave absorbing particle dispersion liquid of the present embodiment is not particularly limited, but for example, it is preferably 0.01% by mass or more and 80% by mass or less. This is because sufficient solar transmittance can be exhibited by setting the content of the electromagnetic wave absorbing particles to 0.01% by mass or more. Also, by setting it to 80% by mass or less, the electromagnetic wave absorbing particles can be uniformly dispersed in the dispersion medium. [Electromagnetic wave absorbing particle dispersion] Next, a configuration example of the electromagnetic wave absorbing particle dispersion of the present embodiment will be described.
[0093] The electromagnetic wave absorbing particle dispersion of the present embodiment includes the above-described electromagnetic wave absorbing particles and a solid medium. And in the electromagnetic wave absorbing particle dispersion of the present embodiment, it is preferable that the electromagnetic wave absorbing particles are dispersed in the solid medium.
[0094] Note that the above-described electromagnetic wave absorbing particles are electromagnetic wave absorbing particles containing cesium tungstate oxide represented by the general formula Cs x W 1-y O 3-z (0.2 ≤ x ≤ 0.4, 0 < y ≤ 0.4, 0 < z ≤ 0.46) and having an orthorhombic or hexagonal crystal structure. Since the details have already been described, the description will be omitted here.
[0095] Hereinafter, the electromagnetic wave absorbing particle dispersion according to the present embodiment will be described in the order of (1) solid medium, (2) manufacturing method, (3) additive, and (4) application example. (1) Solid medium Examples of the solid medium include medium resins such as thermoplastic resins, thermosetting resins, and ultraviolet curable resins. That is, as the solid medium, a resin can be preferably used.
[0096] The specific material of the medium resin is not particularly limited, but is preferably, for example, one resin selected from the group consisting of polyester resin, polycarbonate resin, acrylic resin, styrene resin, polyamide resin, polyethylene resin, vinyl chloride resin, olefin resin, epoxy resin, polyimide resin, fluororesin, ethylene-vinyl acetate copolymer, polyvinyl acetal resin, and ultraviolet curing resin, or a mixture of two or more resins selected from the group. As the polyester resin, polyethylene terephthalate resin can be preferably used.
[0097] These medium resins may also contain a polymeric dispersant having, in the main skeleton, one or more functional groups selected from an amine-containing group, a hydroxyl group, a carboxyl group, and an epoxy group.
[0098] The solid medium is not limited to a resin medium, and a binder using a metal alkoxide can also be used as the solid medium. Representative examples of the metal alkoxide include alkoxides of Si, Ti, Al, Zr, etc. By subjecting the binder using these metal alkoxides to hydrolysis and condensation polymerization by heating, etc., it is also possible to make the solid medium into an electromagnetic wave absorbing particle dispersion containing an oxide.
[0099] The content ratio of the electromagnetic wave absorbing particles in the electromagnetic wave absorbing particle dispersion according to this embodiment is not particularly limited, but the electromagnetic wave absorbing particle dispersion preferably contains 0.001% by mass or more and 80% by mass or less of the electromagnetic wave absorbing particles.
[0100] The shape of the electromagnetic wave absorbing particle dispersion of this embodiment is not particularly limited, but the electromagnetic wave absorbing particle dispersion of this embodiment preferably has a sheet, board, or film shape, because the electromagnetic wave absorbing particle dispersion in the sheet, board, or film shape can be applied to various applications. (2) Method for producing electromagnetic wave absorbing particle dispersion The method for producing the electromagnetic wave absorbing particle dispersion of this embodiment will be described below. Note that the method for producing the electromagnetic wave absorbing particle dispersion is merely illustrated as a configuration example, and the method for producing the electromagnetic wave absorbing particle dispersion described above is not limited to the following configuration example.
[0101] The electromagnetic wave absorbing particle dispersion of this embodiment can be produced, for example, by using a master batch. In this case, the method for producing the electromagnetic wave absorbing particle dispersion of this embodiment can also include, for example, the following master batch production step.
[0102] A masterbatch preparation process in which a masterbatch is obtained in which electromagnetic wave absorbing particles are dispersed in a solid medium.
[0103] In the master batch preparation step, a master batch can be prepared in which the electromagnetic wave absorbing particles are dispersed in a solid medium.
[0104] There is no particular limitation on the specific method for producing the master batch. For example, the master batch can be produced by dispersing an electromagnetic wave absorbing particle dispersion or electromagnetic wave absorbing particles in a solid medium and pelletizing the solid medium.
[0105] As the electromagnetic wave absorbing particles, an electromagnetic wave absorbing particle dispersion powder obtained by removing the liquid medium from an electromagnetic wave absorbing particle dispersion liquid can also be used.
[0106] For example, a mixture is prepared by uniformly mixing an electromagnetic wave absorbing particle dispersion, electromagnetic wave absorbing particles, or electromagnetic wave absorbing particle dispersion powder with a solid medium powder or pellets, and other additives as necessary. The mixture is then kneaded in a vented single-screw or twin-screw extruder, and processed into pellets by cutting melt-extruded strands, thereby producing a master batch. In this case, the shape of the pellets can be cylindrical or prismatic. In addition, when producing pellets, it is also possible to use the so-called hot-cut method in which the molten extrudate is directly cut. In this case, the pellets generally have a shape close to a sphere.
[0107] When the electromagnetic wave absorbing particle dispersion is used as a raw material in the master batch preparation step, it is preferable to reduce or remove the liquid medium derived from the electromagnetic wave absorbing particle dispersion. In this case, the degree to which the liquid medium contained in the electromagnetic wave absorbing particle dispersion is removed is not particularly limited. For example, it is preferable to remove the liquid medium from the electromagnetic wave absorbing particle dispersion or the like to an amount that is allowable to remain in the master batch. When a liquid plasticizer is used as the liquid medium, the entire amount of the liquid plasticizer may remain in the electromagnetic wave absorbing particle dispersion.
[0108] There is no particular limitation on the method for reducing and removing the liquid medium contained in the electromagnetic wave absorbing particle dispersion from the electromagnetic wave absorbing particle dispersion or a mixture of the electromagnetic wave absorbing particle dispersion and a solid medium. For example, it is preferable to dry the electromagnetic wave absorbing particle dispersion or the like under reduced pressure. Specifically, the electromagnetic wave absorbing particle dispersion or the like is dried under reduced pressure while stirring, and the electromagnetic wave absorbing particle-containing composition and the liquid medium components are separated. An example of the device used for the reduced pressure drying is a vacuum stirring type dryer, but any device having the above functions may be used, and is not particularly limited. Furthermore, the pressure value during the reduction in pressure in the drying process is appropriately selected.
[0109] The reduced pressure drying method is preferably used because it improves the efficiency of removing the liquid medium and the like derived from the electromagnetic wave absorbing particle dispersion, and because the electromagnetic wave absorbing particle dispersion powder obtained after reduced pressure drying and the raw material electromagnetic wave absorbing particle dispersion liquid are not exposed to high temperatures for a long period of time, and therefore the electromagnetic wave absorbing particle dispersion powder and the electromagnetic wave absorbing particles dispersed in the electromagnetic wave absorbing particle dispersion liquid do not aggregate. Furthermore, the productivity of the electromagnetic wave absorbing particle dispersion powder and the like is increased, and it is easy to recover the evaporated solvent such as the liquid medium, which is also preferable from an environmental perspective.
[0110] In the electromagnetic wave absorbing particle dispersion powder etc. obtained after the drying step, it is preferable to thoroughly remove the solvent component having a boiling point of 120°C or less. For example, it is preferable that the remaining amount of the solvent component is 2.5 mass% or less. If the remaining solvent component is 2.5 mass% or less, when the electromagnetic wave absorbing particle dispersion powder etc. is processed into, for example, an electromagnetic wave absorbing particle dispersion, no air bubbles are generated, and the appearance and optical properties are maintained in a good condition. In addition, if the remaining solvent component in the electromagnetic wave absorbing particle dispersion powder is 2.5 mass% or less, aggregation due to natural drying of the remaining solvent component does not occur during long-term storage in the state of the electromagnetic wave absorbing particle dispersion powder, and long-term stability is maintained.
[0111] The dispersion concentration of the obtained master batch can be adjusted by adding a solid medium and kneading the mixture while maintaining the dispersed state of the electromagnetic wave absorbing particles contained in the electromagnetic wave absorbing particle dispersion.
[0112] Furthermore, the method for producing the electromagnetic wave absorbing particle dispersion of the present embodiment may, if necessary, include a molding step of molding the obtained master batch or the master batch to which a solid medium has been added as described above, to obtain an electromagnetic wave absorbing particle dispersion of a desired shape.
[0113] The specific method for molding the electromagnetic wave absorbing particle dispersion is not particularly limited, but for example, known methods such as extrusion molding and injection molding can be used.
[0114] In the molding step, for example, an electromagnetic wave absorbing particle dispersion can be produced in the shape of a sheet, a board, or a film, which is molded into a flat or curved shape. The method for molding into a sheet, board, or film shape is not particularly limited, and various known methods can be used. For example, a calendar roll method, an extrusion method, a casting method, an inflation method, etc. can be used.
[0115] The method for producing the electromagnetic wave absorbing particle dispersion of the present embodiment is not limited to the embodiment having the above-mentioned master batch production step.
[0116] For example, the method for producing the electromagnetic wave absorbing particle dispersion of the present embodiment may have the following steps.
[0117] A precursor liquid preparation process in which a solid medium monomer, oligomer, and an uncured liquid solid medium precursor are mixed with electromagnetic wave absorbing particles (electromagnetic wave absorbing particle dispersion powder) or an electromagnetic wave absorbing particle dispersion liquid to prepare an electromagnetic wave absorbing particle dispersion precursor liquid.
[0118] a process for producing an electromagnetic wave absorbing particle dispersion in which the solid medium precursor such as the monomer is cured by a chemical reaction such as condensation or polymerization to produce an electromagnetic wave absorbing particle dispersion;
[0119] For example, when an acrylic resin is used as the solid medium, an electromagnetic wave absorbing particle dispersion precursor liquid can be obtained by mixing an acrylic monomer or an acrylic ultraviolet curing resin with electromagnetic wave absorbing particles.
[0120] Next, the electromagnetic wave absorbing particle dispersion precursor liquid is filled into a predetermined mold or the like and radical polymerization is carried out to obtain an electromagnetic wave absorbing particle dispersion using an acrylic resin.
[0121] When a resin that hardens by crosslinking is used as the solid medium, a dispersion can be obtained by subjecting an electromagnetic wave absorbing particle dispersion precursor liquid to a crosslinking reaction, as in the case of using the acrylic resin described above.
[0122] (3) Additives When a medium resin is used as the solid medium, the electromagnetic wave absorbing particle dispersion of this embodiment may also contain known additives (additives) that are usually added to these resins, such as plasticizers, flame retardants, coloring inhibitors, and fillers, etc. However, as described above, the solid medium is not limited to the medium resin, and a binder using a metal alkoxide may also be used.
[0123] The shape of the electromagnetic wave absorbing particle dispersion according to this embodiment is not particularly limited, but as described above, it can be in the form of, for example, a sheet, board, or film.
[0124] When an electromagnetic wave absorbing particle dispersion in a sheet, board, or film shape is used as an intermediate layer of a transparent substrate such as laminated glass, the solid medium contained in the electromagnetic wave absorbing particle dispersion may not have sufficient flexibility or adhesion to the transparent substrate as it is. In this case, it is preferable that the electromagnetic wave absorbing particle dispersion contains a plasticizer. Specifically, for example, when the solid medium is a polyvinyl acetal resin and used for the above-mentioned applications, it is preferable that the electromagnetic wave absorbing particle dispersion further contains a plasticizer.
[0125] As the above-mentioned plasticizer, a substance used as a plasticizer in the solid medium used in the electromagnetic wave absorbing particle dispersion of this embodiment can be used. For example, examples of plasticizers used in the electromagnetic wave absorbing particle dispersion made of polyvinyl acetal resin include plasticizers that are compounds of monohydric alcohols and organic acid esters, ester-based plasticizers such as polyhydric alcohol organic acid ester compounds, and phosphoric acid-based plasticizers such as organic phosphoric acid-based plasticizers. It is preferable that any of the plasticizers is liquid at room temperature. Among them, plasticizers that are ester compounds synthesized from polyhydric alcohols and fatty acids are preferable. (4) Application Examples The electromagnetic wave absorbing particle dispersion of this embodiment can be used in various aspects, and its use and application aspects are not particularly limited. Hereinafter, as application examples of the electromagnetic wave absorbing particle dispersion of this embodiment, an electromagnetic wave absorbing transparent substrate, an electromagnetic wave absorbing intermediate film, and an electromagnetic wave absorbing laminate will be described. (4-1) Electromagnetic wave absorbing transparent substrate The electromagnetic wave absorbing transparent substrate of this embodiment comprises a transparent substrate and an electromagnetic wave absorbing layer on at least one surface of the transparent substrate, and the electromagnetic wave absorbing layer can be the electromagnetic wave absorbing particle dispersion described above.
[0126] The electromagnetic wave absorbing transparent substrate of this embodiment may have a transparent substrate as described above. As the transparent substrate, for example, one or more types selected from a transparent film substrate and a transparent glass substrate may be preferably used.
[0127] The film substrate is not limited to a film shape, and may be, for example, a board shape or a sheet shape. As the material of the film substrate, one or more selected from polyester resin, acrylic resin, urethane resin, polycarbonate resin, polyethylene resin, ethylene vinyl acetate copolymer, vinyl chloride resin, fluororesin, etc. can be suitably used, and can be used according to various purposes. However, as the material of the film substrate, polyester resin is preferable, and in particular polyethylene terephthalate resin (PET resin) is more preferable. That is, the film substrate is preferably a polyester resin film, and more preferably a polyethylene terephthalate resin film.
[0128] When a film substrate is used as the transparent substrate, the surface of the film substrate is preferably subjected to a surface treatment in order to facilitate adhesion of the electromagnetic wave absorbing layer.
[0129] In order to improve the adhesion between the glass substrate or film substrate and the electromagnetic wave absorbing layer, it is also preferable to form an intermediate layer on the glass substrate or film substrate and then form the electromagnetic wave absorbing layer on the intermediate layer. The intermediate layer is not particularly limited in structure and may be, for example, a polymer film, a metal layer, an inorganic layer (e.g., an inorganic oxide layer such as silica, titania, zirconia, etc.), an organic / inorganic composite layer, etc.
[0130] The electromagnetic wave absorbing particle dispersion has already been described, and therefore the description thereof will be omitted here. The shape of the electromagnetic wave absorbing particle dispersion is not particularly limited, but it is preferable that the dispersion has a sheet shape, a board shape, or a film shape, for example.
[0131] A method for producing the electromagnetic wave-absorbing transparent substrate of this embodiment will be described.
[0132] The electromagnetic wave absorbing transparent substrate of this embodiment can be produced, for example, by forming an electromagnetic wave absorbing layer, which is an electromagnetic wave absorbing particle dispersion in which electromagnetic wave absorbing particles are dispersed in a solid medium, on a transparent substrate using the electromagnetic wave absorbing particle dispersion liquid described above.
[0133] Therefore, the method for producing the electromagnetic wave absorbing transparent substrate of this embodiment can include, for example, the following steps.
[0134] A coating step of coating the surface of a transparent substrate with a coating liquid containing the above-mentioned electromagnetic wave absorbing particle dispersion liquid. An electromagnetic wave absorbing layer forming step of forming an electromagnetic wave absorbing layer after evaporating the liquid medium in the coating liquid.
[0135] The coating liquid used in the coating step can be prepared, for example, by adding and mixing a resin, a solid medium such as a metal alkoxide, or a solid medium precursor to the above-mentioned electromagnetic wave absorbing particle dispersion liquid.
[0136] The solid medium precursor means one or more selected from the solid medium monomer, oligomer, and uncured solid medium as described above.
[0137] When an electromagnetic wave absorbing layer, which is a coating film, is formed on a transparent substrate, the electromagnetic wave absorbing layer is in a state in which cesium tungsten oxide particles are dispersed in a solid medium. Therefore, the electromagnetic wave absorbing layer becomes an electromagnetic wave absorbing particle dispersion. In this way, an electromagnetic wave absorbing transparent substrate can be produced by providing an electromagnetic wave absorbing particle dispersion on the surface of the transparent substrate.
[0138] The solid medium and the solid medium precursor have been described in (1) the electromagnetic wave absorbing particle dispersion and (2) the method for producing the electromagnetic wave absorbing particle dispersion, and therefore description thereof will be omitted here.
[0139] In order to provide an electromagnetic wave absorbing layer on a transparent substrate, the method of applying a coating liquid on the transparent substrate is not particularly limited as long as the coating liquid can be uniformly applied to the surface of the transparent substrate. Examples of the method include bar coating, gravure coating, spray coating, dip coating, spin coating, screen printing, roll coating, flow coating, etc.
[0140] Here, a procedure for producing an electromagnetic wave absorbing layer on the surface of a transparent substrate will be described using, as an example, an ultraviolet curable resin as the medium resin, which is applied by a bar coating method to form an electromagnetic wave absorbing layer.
[0141] The coating solution, the concentration of which and the amount of additives are appropriately adjusted so as to have a suitable leveling property, is applied onto the transparent substrate using a wire bar with a bar number that can satisfy the thickness of the electromagnetic wave absorbing layer and the content of the electromagnetic wave absorbing particles as intended. Then, after removing the solvent such as the liquid medium contained in the coating solution by drying, the coating solution is cured by irradiating it with ultraviolet light, thereby forming a coating layer that is an electromagnetic wave absorbing layer on the transparent substrate.
[0142] Drying conditions for the coating film vary depending on the type and proportion of each component and solvent, but are usually for 20 seconds to 10 minutes at a temperature of 60° C. to 140° C. There are no particular limitations on the ultraviolet ray irradiation, and an ultraviolet ray exposure device such as an ultra-high pressure mercury lamp can be suitably used.
[0143] In addition, the adhesion between the substrate and the electromagnetic wave absorbing layer, the smoothness of the coating film during coating, the drying property of the organic solvent, etc. can be manipulated by the pre- and post-processes (pre- and post-processes) before and after the formation of the electromagnetic wave absorbing layer. Examples of the pre- and post-processes include a surface treatment process of the substrate, a pre-baking process (pre-heating of the substrate), and a post-baking process (post-heating of the substrate), and can be appropriately selected. The heating temperature in the pre-baking process and the post-baking process is preferably, for example, 80° C. or higher and 200° C. or lower, and the heating time is 30 seconds or higher and 240 seconds or lower.
[0144] The method for producing the electromagnetic wave absorbing transparent substrate of this embodiment is not limited to the above-mentioned method. Another example of the method for producing the electromagnetic wave absorbing transparent substrate of this embodiment includes the following steps.
[0145] An electromagnetic wave absorbing particle dispersion coating and drying step in which the above-mentioned electromagnetic wave absorbing particle dispersion is coated on the surface of a transparent substrate and dried. A binder application and curing process in which a binder using a solid medium such as a resin or a metal alkoxide, or a solid medium precursor is applied onto the surface on which the electromagnetic wave absorbing particle dispersion has been applied, and then cured.
[0146] In this case, a film having electromagnetic wave absorbing particles dispersed therein is formed on the surface of the transparent substrate by the steps of coating and drying the electromagnetic wave absorbing particle dispersion. The electromagnetic wave absorbing particle dispersion can be coated by the same method as that explained for the coating step in the above-mentioned method for producing an electromagnetic wave absorbing transparent substrate.
[0147] Then, a binder is applied onto the film in which the electromagnetic wave absorbing particles are dispersed, and then cured, so that the cured binder is disposed between the electromagnetic wave absorbing particles, thereby forming an electromagnetic wave absorbing layer.
[0148] The electromagnetic wave absorbing transparent substrate may further have a coating layer on the surface of the electromagnetic wave absorbing particle dispersion, i.e., may have a multilayer film.
[0149] The coating layer can be a coating film of an oxide containing one or more selected from, for example, Si, Ti, Zr, and Al. In this case, the coating layer can be formed, for example, by applying a coating liquid containing one or more selected from an alkoxide containing one or more of Si, Ti, Zr, and Al, and a partial hydrolysis polycondensate of the alkoxide, onto the electromagnetic wave absorbing layer, and then heating the coating liquid.
[0150] By providing a coating layer, the coating component fills the gaps between the accumulated electromagnetic wave absorbing particles in the first layer to form a film and suppress the refraction of visible light, which reduces the haze value of the film and improves the visible light transmittance. In addition, the adhesion of the electromagnetic wave absorbing particles to the substrate can be improved.
[0151] Here, as a method for forming a coating film made of an alkoxide containing one or more of Si, Ti, Zr, and Al, or a partial hydrolysis and condensation polymerization product thereof, on the electromagnetic wave absorbing particles alone or on a film containing the electromagnetic wave absorbing particles, a coating method is preferred from the viewpoints of ease of film formation operation and cost.
[0152] The coating liquid used in the above coating method can be preferably one containing at least one of alkoxides of Si, Ti, Zr, and Al in a solvent such as water or alcohol, or at least one of partial hydrolysis polycondensates of the alkoxides. The content of the alkoxides in the above coating liquid is not particularly limited, but is preferably 40 mass% or less in terms of oxide in the coating obtained after heating. In addition, the pH can be adjusted by adding an acid or alkali as necessary.
[0153] The coating liquid is applied as a second layer on a film mainly composed of electromagnetic wave absorbing particles, and then heated to easily form an oxide film containing one or more selected from Si, Ti, Zr, and Al, which is a coating layer. It is also preferable to use an organosilazane solution as a binder component used in the coating liquid according to this embodiment or as a component of the coating liquid.
[0154] The electromagnetic wave absorbing particle dispersion liquid containing one or more metal alkoxides of Si, Ti, Zr, and Al and their hydrolysis polymers as the inorganic binder or coating film, and the heating temperature of the substrate after coating with the coating liquid are not particularly limited. For example, the substrate heating temperature is preferably 100° C. or higher, and more preferably the heating temperature is higher than the boiling point of the solvent in the coating liquid such as the electromagnetic wave absorbing particle dispersion liquid.
[0155] This is because the polymerization reaction of the metal alkoxide or the hydrolysis polymer of the metal alkoxide contained in the coating film can be completed when the substrate heating temperature is 100° C. or higher. In addition, when the substrate heating temperature is 100° C. or higher, the solvent water or organic solvent hardly remains in the film, so that these solvents do not cause a decrease in the visible light transmittance of the film after heating.
[0156] The thickness of the electromagnetic wave absorbing layer on the transparent substrate of the electromagnetic wave absorbing transparent substrate of this embodiment is not particularly limited, but is preferably 10 μm or less in practical use, more preferably 6 μm or less, because if the thickness of the electromagnetic wave absorbing layer is 10 μm or less, it not only exhibits sufficient pencil hardness and has abrasion resistance, but also prevents process abnormalities such as warping of the substrate film during evaporation of the solvent and hardening of the binder in the electromagnetic wave absorbing layer. (4-2) Electromagnetic wave absorbing interlayer film, electromagnetic wave absorbing laminate The electromagnetic-wave absorbing laminate of this embodiment may have a laminate structure including the electromagnetic-wave absorbing particle dispersion and a transparent substrate as described above. The electromagnetic-wave absorbing laminate of this embodiment may be a laminate having the electromagnetic-wave absorbing particle dispersion and a transparent substrate as elements and stacking these together.
[0157] An example of the electromagnetic wave absorbing laminate is a laminate of two or more transparent substrates and the above-mentioned electromagnetic wave absorbing particle dispersion. In this case, the electromagnetic wave absorbing particle dispersion is disposed between the transparent substrates and can be used as an electromagnetic wave absorbing intermediate film.
[0158] In this case, the electromagnetic wave absorbing interlayer film preferably has any one of a sheet shape, a board shape, and a film shape.
[0159] The transparent substrate may be one or more selected from the group consisting of glass sheets, plastic sheets, and plastic films that are transparent in the visible light range.
[0160] When plastic is used as the transparent substrate, the material of the plastic is not particularly limited and can be selected according to the application, and can be, for example, one or more types selected from polycarbonate resin, acrylic resin, polyester resin, polyamide resin, vinyl chloride resin, olefin resin, epoxy resin, polyimide resin, ionomer resin, fluororesin, etc. As the polyester resin, polyethylene terephthalate resin can be preferably used.
[0161] The transparent substrate may contain particles having a solar radiation shielding function. As the particles having a solar radiation shielding function, electromagnetic wave absorbing particles having near-infrared shielding properties can be used.
[0162] By using the electromagnetic wave absorbing particle dispersion described above as a constituent member of an intermediate layer sandwiched between multiple transparent substrates, a solar radiation shielding laminated structure, which is a type of electromagnetic wave absorbing laminate that transmits visible light while having a near-infrared shielding function, can be obtained.
[0163] The electromagnetic wave absorbing laminate can also be obtained by bonding and integrating a plurality of transparent substrates facing each other with the electromagnetic wave absorbing particle dispersion therebetween by a known method.
[0164] When the above-mentioned electromagnetic wave absorbing particle dispersion is used as an electromagnetic wave absorbing intermediate film, the solid medium may be the same as that described for the electromagnetic wave absorbing particle dispersion. However, from the viewpoint of increasing the adhesive strength between the electromagnetic wave absorbing intermediate film and the transparent substrate, the solid medium is preferably a polyvinyl acetal resin.
[0165] The electromagnetic wave absorbing interlayer film of this embodiment can be produced by the above-mentioned method for producing an electromagnetic wave absorbing particle dispersion, and can be, for example, an electromagnetic wave absorbing interlayer film having any one of a sheet shape, a board shape, or a film shape.
[0166] In addition, when the electromagnetic wave absorbing interlayer does not have sufficient flexibility or adhesion to the transparent substrate, it is preferable to add a liquid plasticizer for the medium resin. For example, when the medium resin used in the electromagnetic wave absorbing interlayer is a polyvinyl acetal resin, the addition of a liquid plasticizer for polyacetal resin is beneficial for improving adhesion to the transparent substrate.
[0167] As the plasticizer, a substance that is used as a plasticizer for a medium resin can be used. For example, as the plasticizer used in the infrared shielding film made of polyvinyl acetal resin, there are a plasticizer that is a compound of a monohydric alcohol and an organic acid ester, an ester-based plasticizer such as a polyhydric alcohol organic acid ester compound, and a phosphoric acid-based plasticizer such as an organic phosphoric acid-based plasticizer. It is preferable that any plasticizer is liquid at room temperature. Among them, a plasticizer that is an ester compound synthesized from a polyhydric alcohol and a fatty acid is preferable.
[0168] The electromagnetic wave absorbing interlayer film may also contain at least one selected from the group consisting of a silane coupling agent, a metal salt of a carboxylic acid, a metal hydroxide, and a metal carbonate. The metal constituting the metal salt of a carboxylic acid, the metal hydroxide, and the metal carbonate is not particularly limited, but is preferably at least one selected from sodium, potassium, magnesium, calcium, manganese, cesium, lithium, rubidium, and zinc. In the electromagnetic wave absorbing interlayer film, the content of at least one selected from the group consisting of a metal salt of a carboxylic acid, a metal hydroxide, and a metal carbonate is preferably 1% by mass or more and 100% by mass or less relative to the electromagnetic wave absorbing particles.
[0169] Furthermore, the electromagnetic wave absorbing interlayer film may contain, in addition to the electromagnetic wave absorbing particles described above, at least one of oxide particles, composite oxide particles, and boride particles containing two or more elements selected from the group consisting of Sb, V, Nb, Ta, W, Zr, F, Zn, Al, Ti, Pb, Ga, Re, Ru, P, Ge, In, Sn, La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Tb, Lu, Sr, and Ca. The electromagnetic wave absorbing interlayer film may contain such particles in an amount of 5% by mass to 95% by mass, assuming that the total amount of the particles and the electromagnetic wave absorbing particles is 100% by mass.
[0170] The electromagnetic wave absorbing laminate may contain an ultraviolet absorbing agent in at least one layer of the intermediate film disposed between the transparent substrates. The ultraviolet absorbing agent may be one or more selected from a compound having a malonic acid ester structure, a compound having an oxalic acid anilide structure, a compound having a benzotriazole structure, a compound having a benzophenone structure, a compound having a triazine structure, a compound having a benzoate structure, a compound having a hindered amine structure, and the like.
[0171] Incidentally, it goes without saying that the intermediate layer of the electromagnetic wave absorbing laminate may be composed only of the electromagnetic wave absorbing intermediate film according to this embodiment.
[0172] The electromagnetic wave absorbing interlayer film described here is one aspect of the electromagnetic wave absorbing particle dispersion. The electromagnetic wave absorbing particle dispersion according to this embodiment can be used without being sandwiched between two or more transparent substrates that transmit visible light. In other words, the electromagnetic wave absorbing particle dispersion according to this embodiment can function alone as an electromagnetic wave absorbing particle dispersion.
[0173] The electromagnetic wave absorbing laminate according to this embodiment is not limited to the above-mentioned form in which an electromagnetic wave absorbing particle dispersion is disposed between transparent substrates, and may have any configuration as long as it has a laminate structure including an electromagnetic wave absorbing particle dispersion and a transparent substrate. EXAMPLES
[0174] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0175] First, the evaluation methods used in the following Examples and Comparative Examples will be described. (chemical analysis) The chemical analysis of the obtained electromagnetic wave absorbing particles was performed by atomic absorption spectrometry (AAS) for Cs and by inductively coupled plasma optical emission spectrometry (ICP-OES) for W (tungsten). For O, analysis was carried out using a light element analyzer (manufactured by LECO, model ON-836). The sample was melted in He gas and the CO gas reacted with the carbon in the crucible was quantified by IR absorption spectrometry. In Table 1, the composition ratios are calculated with W (tungsten) set to 1 based on the content ratios of each element determined by chemical analysis and are also shown. In the following Examples 1 to 13, powders that are electromagnetic wave absorbing particles containing cesium tungsten composite oxides with W deficiency were obtained. Therefore, for powders A to M, which are electromagnetic wave absorbing particles obtained in Examples 1 to 13, the composition ratios obtained by multiplying the composition ratios shown in Table 1 with W set to 1 by values corresponding to the W deficiency all satisfy the general formula Cs x W 1-y O 3-z (0.2 ≦ x ≦ 0.4, 0 < y ≦ 0.4, 0 < z ≦ 0.46). (X-ray diffraction measurement) X-ray diffraction measurement was carried out by powder XRD measurement using Cu-Kα rays with a Spectris X'Pert-PRO / MPD device.
[0176] The diffraction angle was calibrated with a standard sample (NIST640e) before measurement. Then, Rietveld analysis was performed on the obtained XRD diffraction pattern to determine the lattice constants of the crystal phases. In Table 1, when orthorhombic crystals are included, they are denoted as R, and when hexagonal crystals are included, they are denoted as H. When both orthorhombic and hexagonal crystals are included, they are denoted as R + H in Table 1.
[0177] In the case of a mixed phase of orthorhombic and hexagonal crystals, the lattice constants for each phase were determined. Then, the lattice constant of the orthorhombic crystal was converted to the lattice constant of the hexagonal crystal according to the following lattice correspondence model. The correspondence of the lattice change between the orthorhombic and hexagonal crystals was extracted from the model of Solodovnikov 1998 (Non-Patent Document 4), the formula 4a orth 2 +b orth 2 = 64ahex 2 = 64b hex 2 , c orth =c hex The lattice constant in hexagonal crystal was calculated using the formula: orth , b orth , c orth means the length of the a-axis, b-axis, and c-axis of the orthorhombic crystal. hex , b hex , c hex means the lengths of the a-axis, b-axis, and c-axis of the hexagonal crystal. (Optical properties of electromagnetic wave absorbing transparent substrate) The visible light transmittance (VLT) and solar transmittance (ST) of the electromagnetic wave absorbing transparent substrate were measured in accordance with ISO 9050 and JIS R 3106. Specifically, the transmittance was measured using a spectrophotometer U-4100 manufactured by Hitachi, Ltd., and calculated by multiplying it by a coefficient according to the spectrum of sunlight. The transmittance was measured at 5 nm intervals in the wavelength range of 300 nm to 2100 nm. * a * b * The color index was calculated in accordance with JIS Z 8701 by calculating the tristimulus values X, Y, and Z for a D65 standard light source and a light source angle of 10°, and then calculated from the tristimulus values in accordance with JIS Z 8729. The RGB color index was also calculated from the tristimulus values in the same manner. [Example 1] Cesium carbonate (Cs 2 CO 3 ) and tungsten trioxide (WO 3 ) in molar ratio of Cs 2 CO 3 :WO 3 The mixture was weighed, mixed, and kneaded to give a ratio of 2:11, and placed in a carbon boat, and heated twice in a tubular furnace in the air at 850°C for 20 hours to obtain Powder A', which is a very light greenish white powder. Note that when heating, the powder was taken out once after heating for 20 hours at 850°C, crushed and mixed, and then reheated under the same conditions.
[0178] The obtained white powder, Powder A', was evaluated as follows.
[0179] The X-ray powder diffraction pattern shows only slight Cs 6 W 11 O 36 There are some mixed in, but it's mostly Cs 4 W 11 O 35 It was identified as monophasic (ICDD 00-51-1891).
[0180] The lattice constants were measured to be a = 14.6733 Å, b = 52.3841 Å, and c = 7.7424 Å. These values are very close to the values of a = 14.6686 Å, b = 52.3971 Å, and c = 7.7356 Å given by Solodovnikov (Non-Patent Document 4). Chemical analysis of the white powder indicated that it was Cs 0.36 WO 3.18 This almost coincided with the weighed composition.
[0181] Next, the obtained white powder, Powder A', was observed by TEM. When the selected area electron diffraction pattern was taken, an orthorhombic spot pattern was obtained. Figure 4 shows the spot pattern taken from the c-axis direction of the orthorhombic crystal. A b / 8 periodicity was observed in the b-axis direction, confirming the presence of missing planes of W and O. In addition, the streaks running in the b-axis direction revealed the presence of some planar defects on the b-plane. The spot pattern of this c-axis crystal zone axis is close to 6-fold symmetry, but the angle between the (480) and (4-80) spots is 52.2°, which is deviated from 60° in the case of 6-fold symmetry, and it is thought that the deviation from 6-fold symmetry is due to the missing planes of W and O that fall into the b / 8 period.
[0182] The resulting white powder, Cs 4 W 11 O 35 The powder was spread thinly and evenly on a carbon boat, placed in a tubular furnace, and heated in an Ar gas stream from room temperature to 800°C. While maintaining the temperature at 800°C, 1 vol% H 2 The gas flow was switched to a mixture of 10 ... 2The gas was stopped and the mixture was gradually cooled to 100°C using only Ar gas flow, after which the Ar gas flow was stopped and the mixture was gradually cooled to room temperature and powder A was taken out. The color of the taken out powder A was light blue.
[0183] The XRD pattern of powder A showed a two-phase mixed pattern of orthorhombic and hexagonal. The lattice constants of each phase were determined by the Rietveld method, and the orthorhombic phase had a = 14.6609 Å, b = 52.4040 Å, and c = 7.7419 Å (equivalent values for hexagonal phase were a = 7.5062 Å, c = 7.7419 Å), and the hexagonal phase had a = 7.4170 Å, c = 7.5752 Å. It was confirmed that the c-axis values for both phases were in the range of 7.560 Å ≦ c ≦ 7.750 Å.
[0184] Next, when powder A was observed by TEM, orthorhombic particles and pseudohexagonal particles were observed.
[0185] Here, an electron beam diffraction image of the pseudohexagonal crystal grain is shown in FIG. 5. The pseudohexagonal crystal grain is the
[0001] HEX As shown by the electron diffraction pattern of the zone axis, the diffraction pattern is close to that of a hexagonal crystal. Here, (200) HEX and (110) HEX The interplanar angle was measured to be 59.2°, a value close to that of a hexagonal crystal.
[0186] Next, powder A was observed in STEM-HAADF mode (STEM: scanning transmission electron microscopy, HAADF: High-angle annular dark field).
[0187] Figure 6 shows the HAADF image of a pseudo-hexagonal grain observed from the
[0221] zone axis. In the HAADF mode, atomic particles are observed with a brightness proportional to the atomic number and the probability of the atomic existence in the projection direction, so the (110) grains appear dark in Figure 6. HEX The linear region along the (110) was identified as a vacancy of W, which has the highest atomic number. The trace of such a W vacancy region was observed from a different direction and found to be aligned along the (110) HEXIt was confirmed that the traces spread in a planar manner. In addition, some of the traces with low contrast appear to have contracted linearly.
[0188] In this embodiment, the heat reduction treatment was performed for 5 minutes, which is shorter than the time required for other embodiments described later. ORTH The W defects shrink and undergo a structural transition to a pseudo-hexagonal structure, and in the pseudo-hexagonal structure, the {100} HEX Many W-depleted areas in the process of shrinking were observed on the surface. [Example 2] Powder A' obtained in Example 1 is Cs 4 W 11 O 35 The powder was spread thinly and evenly on a carbon boat, placed in a tubular furnace, and heated in an Ar gas stream from room temperature to 800°C. While maintaining the temperature at 800°C, 1% H 2 The gas flow was switched to a mixed gas flow, and reduction was continued for 15 minutes. 2 The gas was stopped, and the mixture was gradually cooled to 100°C using only Ar gas flow, after which the Ar gas flow was stopped and the mixture was gradually cooled to room temperature, and powder B was taken out. The color of the powder B taken out was blue.
[0189] The XRD pattern of Powder B showed a two-phase mixed pattern of orthorhombic and hexagonal. The lattice constants of each phase were determined by the Rietveld method, and the orthorhombic phase had a = 14.6576 Å, b = 52.4315 Å, and c = 7.7412 Å (equivalent values for hexagonal phase were a = 7.5088 Å, c = 7.7412 Å), and the hexagonal phase had a = 7.4122 Å, c = 7.5940 Å. It was confirmed that the c-axis values for both phases were in the range of 7.560 Å ≦ c ≦ 7.750 Å.
[0190] Next, when powder B was observed by TEM, orthorhombic particles and pseudohexagonal particles were observed, as in the case of powder A obtained in Example 1. The pseudohexagonal particles are shown in FIG. HEX As shown by the electron diffraction pattern of the zone axis, the diffraction pattern is close to that of a hexagonal crystal. Here, (200) HEX and (110) HEXThe interplanar angle was measured to be 59.5°, a value close to that of a hexagonal crystal. [Example 3] Powder A' obtained in Example 1 is Cs 4 W 11 O 35 The powder was spread thinly and evenly on a carbon boat, placed in a tubular furnace, and heated in an Ar gas stream from room temperature to 800°C. While maintaining the temperature at 800°C, 1% H 2 The gas flow was switched to a mixed gas flow, and reduction was performed for 30 minutes. 2 The gas was stopped, and the mixture was gradually cooled to 100°C using only Ar gas flow, after which the Ar gas flow was stopped and the mixture was gradually cooled to room temperature, and powder C was taken out. The color of the taken-out powder C was deep blue.
[0191] The XRD pattern of Powder C showed a two-phase mixed pattern of orthorhombic and hexagonal. The lattice constants of each phase were determined by the Rietveld method, and the orthorhombic phase had a=14.6649Å, b=52.4010Å, c=7.7451Å (equivalent values for hexagonal phase were a=7.5064Å, c=7.7451Å), and the hexagonal phase had a=7.4076Å, c=7.6107Å. The c-axis values for both phases were confirmed to be in the range of 7.560Å≦c≦7.750Å.
[0192] Next, TEM observation of Powder C revealed orthorhombic and pseudohexagonal particles, similar to the case of Powder A obtained in Example 1. The pseudohexagonal particles showed a hexagonal diffraction pattern, as shown in the electron beam diffraction image of the
[0001] zone axis in Figure 8. Here, the (200) HEX and (110) HEX The interplanar angle was measured to be 60.0°, a value for a hexagonal crystal. [Examples 4 to 7] Powder A' obtained in Example 1 is Cs 4 W 11 O 35The reduction time during the reduction treatment of the powder was changed to 35 minutes to 90 minutes as shown in Table 1. Except for the above, Powders D, E, F, and G were produced in the same manner as Powder A in Example 1. Powders D to G all had a deep blue color, and their XRD lattice constants are as shown in the table.
[0193] As shown in Table 1, in Example 4, an orthorhombic phase was also observed, and the c-axis length calculated as a hexagonal phase was 7.7440 Å (Example 4). [Examples 8 to 11] Powder A' obtained in Example 1 is Cs 4 W 11 O 35 The heating temperature and reduction time when the powder was subjected to the heating reduction treatment were changed as shown in Table 1. Specifically, in Example 8, the heating temperature and reduction time were 650°C for 120 minutes, in Example 9, 700°C for 60 minutes, in Example 10, 900°C for 10 minutes, and in Example 11, 950°C for 20 minutes. Except for the above, Powder H, Powder I, Powder J, and Powder K were produced in the same manner as Powder A in Example 1. Light blue, blue, dark blue, and dark blue powders were obtained, respectively. The lattice constants obtained from the XRD patterns of the obtained powders were as shown in Table 1.
[0194] As shown in Table 1, in Examples 8 and 9 and the following Examples 12 and 13, an orthorhombic phase was also observed, and the c-axis lengths converted to hexagonal were 7.7428 Å (Example 8), 7.7471 Å (Example 9), 7.7449 Å (Example 12), and 7.7466 Å (Example 13). [Example 12] Cesium carbonate and tungsten trioxide in a molar ratio of Cs 2 CO 3 :WO 3 The mixture was mixed in a ratio of 3:11, spread thinly and evenly on a carbon boat, placed in a tube furnace, and heated at 850°C for 5 hours to obtain a very light greenish white powder. The main phase of this white powder was Cs 6 W 11 O 36 (ICDD1-70-632), but Cs 4 W 11 O35 It was a mixed phase.
[0195] The resulting white powder was dissolved in 1% H 2 -N 2 The mixture was heat-treated in an air stream at 800°C for 30 minutes to obtain a deep blue powder L.
[0196] The XRD pattern of Powder L showed a two-phase mixed pattern of orthorhombic and hexagonal crystals. The lattice constants obtained from the XRD pattern of Powder L are shown in Table 1. [Example 13] Cesium carbonate and tungsten trioxide in a molar ratio of Cs 2 CO 3 :WO 3 The mixture was mixed at a ratio of 1:6, thinly spread evenly on a carbon boat, placed in a tube furnace, and heated at 850°C for 5 hours to obtain a very light greenish white powder. The main phase of this white powder was Cs 4 W 11 O 35 However, Cs 2 W 6 O 19 It was mixed phase with (ICDD00-045-0522).
[0197] The resulting white powder was dissolved in 1% H 2 -N 2 The mixture was heat-treated in an air stream at 800°C for 30 minutes to obtain a deep blue powder M.
[0198] The XRD pattern of Powder M showed a two-phase mixed pattern of orthorhombic and hexagonal crystals. The lattice constants obtained from the XRD pattern of Powder M are shown in Table 1.
[0199] As shown in the above Examples 1 to 13, the white Cs 4 W 11 O 35 Or Cs 6 W 11 O 36 , Cs 2 W 6 O 19 Contains Cs 4 W 11 O 35When the powder was reduced at high temperature, the color of the powder gradually changed from light blue to blue to dark blue.
[0200] Also Cs 4 W 11 O 35 In the phase, lattice defects including W vacancies exist, and the phase is orthorhombic. However, when this phase is reduced at high temperatures, it was confirmed that the lattice defects including W vacancies disappear and the orthorhombic phase changes to a hexagonal phase. [Example 14] 20% by mass of the powder A produced in Example 1, 10% by mass of an acrylic polymer dispersant having an amine-containing functional group (hereinafter abbreviated as "dispersant a"), and 70% by mass of methyl isobutyl ketone (MIBK) as a solvent were weighed out. These weighed materials were placed in a glass container together with silica beads having a diameter of 0.3 mm, and dispersed and pulverized for 5 hours using a paint shaker to obtain dispersion A.
[0201] Here, the average particle size of the electromagnetic wave absorbing particles in the dispersion A (dispersed particle size measured by a particle size measuring device based on dynamic light scattering, ELS-8000 manufactured by Otsuka Electronics Co., Ltd.) was measured to be 26.4 nm.
[0202] 100 parts by mass of this dispersion A was mixed with 50 parts by mass of ultraviolet curing resin for hard coat (Akonix UV-3701 manufactured by Toa Gosei) to obtain an electromagnetic wave absorbing particle coating liquid. Then, this electromagnetic wave absorbing coating liquid was applied onto a polyethylene terephthalate (PET) resin film (HPE-50 manufactured by Teijin, hereinafter also referred to as "PET film"), which is a transparent film substrate, using a bar coater to form a coating film. Note that the same PET film was used as the transparent substrate in other examples as well.
[0203] The PET film provided with the coating film was dried at 80°C for 5 minutes to evaporate the organic solvent, which was the liquid medium, and then cured with a high-pressure mercury lamp to produce an electromagnetic-wave-absorbing film A provided with a coating layer containing electromagnetic-wave-absorbing particles. Note that the coating layer is an electromagnetic-wave-absorbing layer, and the electromagnetic-wave-absorbing film is one form of an electromagnetic-wave-absorbing transparent substrate.
[0204] The transmittance of the obtained dispersion A was measured using a Hitachi High-Tech U-4100 spectrophotometer, and the molar absorption coefficient was calculated. The profiles are shown in Fig. 9A and Fig. 9B. Fig. 9A shows the molar absorption coefficients of the dispersions of Examples 14 to 20 and Comparative Example 1 prepared using the electromagnetic wave absorbing particles prepared in Examples 1 to 7. Fig. 9B is a partially enlarged view of Fig. 9A. Fig. 9C shows the molar absorption coefficients of the dispersions of Examples 15, 16, 18, 22, 23, and Comparative Example 1 prepared using the electromagnetic wave absorbing particles prepared in Examples 2, 3, 5, 9, and 10.
[0205] According to the profile shown in FIG. 9, absorption in the near infrared region of 0.6 eV to 1.6 eV and transmission in the visible region of 1.6 eV to 3.0 eV were confirmed.
[0206] The visible light transmittance (VLT) and solar radiation transmittance (ST) of the electromagnetic wave absorbing film A were measured to be VLT = 72.3% and ST = 55.3%, respectively, and it was found that the film was transparent to visible light like the dispersion A, and had a near-infrared absorbing effect. The color index of the electromagnetic wave absorbing film A was L * =88.4, a * =-1.4, b * = 8.8, which means that the blue color is very weak and close to neutral, i.e., the color tone is neutral. [Example 15] The powder B produced in Example 2 was dispersed and pulverized in the same manner as in Example 14 to obtain a dispersion liquid B. The dispersed particle size of the particles was 31.4 nm. The molar absorption coefficient profile of this dispersion liquid B is shown in Figures 9A to 9C. The transmittance profile of the dispersion liquid B is shown in Figures 10A and 10B. In deriving the transmittance profile, the transmittance profile was derived from the molar absorption coefficient by the Lambert-Beer equation so that the VLT value was the same as the VLT value of the spectral transmittance of the dispersion liquid A obtained in Example 14. The following Comparative Examples 1 to 3, Example 16, and Example 19 shown in Figures 10A and 10B were derived in the same manner.
[0207] Since the solar radiation shielding effect and the transmitted color change depending on the VLT value of the film, it is necessary to perform their evaluation by adjusting the same VLT. Therefore, the mixing ratio of the dispersion B, the ultraviolet curing resin, and MIBK was adjusted to prepare the coating liquid B so that the VLT value of the spectral transmittance obtained in the electromagnetic-wave-absorbing film of Example 14 was in the almost same VLT range (72.0% to 73.0%). The coating liquid B was applied to a PET film in the same manner as in Example 14, dried, and cured to prepare the electromagnetic-wave-absorbing film B.
[0208] The optical properties of electromagnetic wave absorbing film B were VLT=72.7% and ST=41.6%, respectively, and it was found to have extremely good solar radiation shading properties.
[0209] In addition, the color index of electromagnetic wave absorbing film B is L * =88.5, a * =-3.9, b * = 5.4, and b * The value was positive, and the blue color was weak, showing a color tone close to a neutral color. It can be said that the thin dispersion film of this electromagnetic wave absorbing particle at VLT = 70 to 80%, which is used for automobile windshields, is a film that gives almost no blue tint. [Comparative Example 1] Powder A' obtained in Example 1 is Cs 4 W 11 O 35 The powder was pulverized and dispersed in the same manner as in Example 14 to obtain Dispersion N. Dispersion N was grayish white in color, and the dispersed particle size of the particles in Dispersion N was 30.3 nm. The transmittance profile of Dispersion N is shown in Figs. 10A and 10B.
[0210] In the same manner as in Example 15, the blending ratio of Dispersion Liquid N, UV-curable resin, and MIBK was adjusted to obtain Coating Liquid N, and then Electromagnetic-wave-absorbing Film N was obtained. Meanwhile, the obtained spectroscopic properties of Electromagnetic-wave-absorbing Film N were VLT=72.6% and ST=80.2%, indicating that the film had almost no infrared absorbing effect. [Comparative Example 2] Cesium carbonate (Cs 2 CO 3 ) aqueous solution, tungstic acid (H2 WO 4 ), and tungsten dioxide powder (WO 2 ) to Cs 2 O·5WO 3 ·4WO 2 After thorough mixing, the raw material mixture was thinly and evenly spread on a carbon boat and then heated with N 2 1% H with gas as carrier 2 The temperature was kept at 550°C for 60 minutes under a gas flow, and then 100% N 2 The mixture was then heated to 800°C and held for 1 hour, then cooled to room temperature to obtain powder O. Powder O was deep blue in color. Chemical analysis revealed that the composition was Cs 0.33 WO 2.74 was obtained.
[0211] The XRD pattern of powder O showed a single hexagonal phase. The lattice parameters a = 7.4088 Å and c = 7.6033 Å were obtained by Rietveld analysis. The c-axis lattice parameters were in the favorable range.
[0212] Next, TEM observation revealed no particularly noticeable lattice defects. STEM atomic image observation also revealed no noticeable lattice defects, and no W vacancies.
[0213] Powder O was pulverized and dispersed in the same manner as in Example 15 to obtain Dispersion O. Dispersion O was deep blue in color. The dispersed particle size of the electromagnetic wave absorbing particles in Dispersion O was 25.8 nm. The transmittance profile of Dispersion O is shown in Figs. 10A and 10B.
[0214] In the same manner as in Example 15, the blending ratio of the dispersion O, the ultraviolet curing resin, and MIBK was adjusted to obtain a coating liquid O, and then an electromagnetic wave absorbing film O was obtained.
[0215] The spectral characteristics of the electromagnetic wave absorbing film O are VLT=72.5%, ST=37.5%, and color index L * =88.2, a * =-5.7, b *=-2.8 was obtained. Therefore, the powder and the dispersion have a strong near-infrared absorbing effect, but the electromagnetic wave absorbing film O containing the dispersion has a b * It can be seen that the blue tinge is clearly perceived because the value is negative. [Comparative Example 3] As a reference sample for color tone, neutral In 2 O 3 A dispersion of ITO (Indium Tin Oxide) was prepared. ITO particles are known to have a neutral color tone, but there are various types ranging from slightly blue to brown depending on the reduction method and production method. Here, we used ITO powder (Powder P) manufactured by ENAM, which is close to pure transparency.
[0216] Powder P was pulverized and dispersed in the same manner as in Example 14 to obtain Dispersion P. Dispersion P was light blue in color. The dispersed particle size of the electromagnetic wave absorbing particles in Dispersion P was 35.4 nm. The transmittance profile of Dispersion P is shown in Figs. 10A and 10B.
[0217] In the same manner as in Example 15, the blending ratio of the dispersion P, the ultraviolet curing resin, and MIBK was adjusted to obtain a coating solution P, and then an electromagnetic-wave absorbing film P was obtained. The spectral characteristics of the electromagnetic-wave absorbing film P were VLT=72.7%, ST=47.8%, and color index L * =88.3, a * =-2.2, b * = 12.4. Therefore, the electromagnetic wave absorbing film P containing the dispersion using the ITO powder and the dispersion liquid has a * Since the value is a large positive number, the blueness is very little and it is recognized as a neutral color. However, it was confirmed that the near-infrared absorption effect is about the same as that of Example 15 and is inferior to that of Comparative Example 2. [Examples 16 to 20] Powders C to G produced in Examples 3 to 7 were dispersed and pulverized in the same manner as in Example 14 to obtain Dispersion Liquids C to G. The molar absorption coefficient profile of each dispersion liquid is shown in FIG. 9. The dispersed particle size of each dispersion liquid is shown in Table 2.
[0218] Then, in the same manner as in Example 15, the blending ratio of each dispersion and the ultraviolet curing resin with MIBK was adjusted to obtain Coating Liquid C to Coating Liquid G. Each coating liquid was used to obtain Electromagnetic-wave-absorbing Film C to Electromagnetic-wave-absorbing Film G. The optical properties and color index of each electromagnetic-wave-absorbing film are shown in Table 2.
[0219] In these electromagnetic wave absorbing films, it can be seen that the longer the reduction time at 800℃, the greater the near infrared absorption, while the transmitted color tends to be more blue. However, it was confirmed that in all cases, the color tone was close to neutral.
[0220] As described above, Fig. 10A and Fig. 10B collectively show the transmittance profiles of the dispersions according to Comparative Examples 1 to 3, Examples 15, 16, and 19. Fig. 10B is a partial enlarged view of Fig. 10A.
[0221] The solar transmittance (ST) of the dispersions according to Comparative Examples 1 to 3, Examples 15, 16, and 19 is shown in FIG. 11A, and the color indexes are shown in FIGS. 11B and 11C. In FIGS. 11A to 11C, the t R t means the reduction time at 800°C. For this reason, only some of the parts in Figs. 11A to 11C are explained. R Examples that are the same are the same experimental examples.
[0222] 10A and 10B, Comparative Example 1 has a low transmittance for blue wavelengths but a high transmittance for red wavelengths, and when used as a dispersion film (dispersion body), it appears as a transparent film overall. Conversely, Comparative Example 2 has a high transmittance for blue wavelengths but a large drop in transmittance for red wavelengths, and when used as a dispersion film (dispersion body), it appears as a bluish film overall.
[0223] The dispersions of Examples 15, 16 and 19 are intermediate between those of Comparative Examples 1 and 2, and as the reduction time at 800°C increases, the transmittance at blue wavelengths gradually increases, while the transmittance at red wavelengths tends to rapidly decrease with absorption in the near infrared region. In Example 19, in which the reduction time is 60 minutes at 800°C, the transmittance profile approaches that of Comparative Example 2, but even with the same VLT value, the electromagnetic-wave-absorbing film of Example 19 has a similar transmittance at red wavelengths but a lower transmittance at blue wavelengths, and it can be seen that it has a more neutral color tone.
[0224] In FIG. 11A, it was confirmed that the dispersions of Example 16 and Example 19, in which the reduction time at 800°C was more than 20 minutes, had a better solar radiation shielding effect than the dispersion of Comparative Example 3 using ITO. In addition, when the reduction time at 800°C was 60 minutes, the conventional Cs 0.33 WO 3 The level is almost the same as that of the dispersion liquid of Comparative Example 2 using the above.
[0225] Regarding the color shown in Fig. 11B and Fig. 11C, when the reduction time at 800°C was about 30 minutes or less, * The value is Cs 0.33 WO 3 This is a value significantly on the neutral side compared to Comparative Example 2, which used [Examples 21 to 24] Powders H to K produced in Examples 8 to 11 were dispersed and pulverized in the same manner as in Example 14 to obtain Dispersion Liquid H to Dispersion Liquid K. The dispersed particle diameters of the dispersion liquids are shown in Table 2. Moreover, the molar absorption coefficient profiles of the obtained dispersion liquids are shown in FIG. 9C.
[0226] Then, in the same manner as in the procedure performed in Example 15, the blending ratio of each dispersion, ultraviolet curing resin, and MIBK was adjusted, and coating solutions H to K were prepared so that the VLT of the electromagnetic-wave-absorbing films obtained from each dispersion was 72% to 74%, and then electromagnetic-wave-absorbing films H to K were obtained.
[0227] The optical properties and color indices of these electromagnetic wave absorbing films are shown in Table 2.
[0228] In these electromagnetic wave absorbing films, the reduction temperature and time are different at 650℃ to 950℃, but it can be seen that the higher the degree of high-temperature reduction of the particles, the greater the near-infrared absorption, while the transmitted color tends to be more blue. However, it was confirmed that in all cases, the color tone was close to neutral.
[0229] It was confirmed that there is a trade-off between the blue tendency of the transmitted color and the near-infrared absorption effect, and it is preferable to select an appropriate degree of high-temperature reduction depending on the application. [Examples 25 and 26] Powder L and Powder M prepared in Examples 12 and 13 were dispersed and pulverized in the same manner as in Example 14 to obtain Dispersion Liquid L and Dispersion Liquid M. The dispersed particle diameters of the dispersion liquids are shown in Table 2.
[0230] Then, in the same manner as in the procedure performed in Example 15, the blending ratio of each dispersion, ultraviolet curing resin, and MIBK was adjusted, and Coating Liquid L and Coating Liquid M were adjusted so that the VLT of the electromagnetic-wave-absorbing film obtained from each dispersion was about 72%, and then electromagnetic-wave-absorbing Film L and electromagnetic-wave-absorbing Film M were obtained.
[0231] The optical properties and color indexes of these electromagnetic wave absorbing films are shown in Table 2. In these electromagnetic wave absorbing films, the composition and structure of the raw material powder are Cs 6 W 11 O 36 , or Cs 2 W 6 O 19 Contains Cs 4 W 11 O 35 Although it is slightly different from the powder of (1), the change from orthorhombic to hexagonal crystals accompanying high-temperature reduction basically involves the same content, and it is considered that the characteristics of the electromagnetic wave absorbing film mainly depend on the reduction conditions at high temperatures.
[0232] That is, the raw material powder is tungsten oxide Cs 2 O·nWO 3It can be seen that even if the degree of high-temperature reduction is changed within the range (3.6≦n≦9.0), the higher the degree of high-temperature reduction of the particles, the greater the near-infrared absorption, while the transmitted color tends to be more blue. There is a trade-off between the blue tendency of the transmitted color and the near-infrared absorption effect, so an appropriate degree of high-temperature reduction can be selected depending on the application. [Example 27] Dispersion C prepared in Example 16, an ultraviolet curing resin (Aronix UV3701 manufactured by Toa Gosei Co., Ltd.), and MIBK were mixed to prepare coating solution A. The obtained coating solution was applied to a soda lime glass substrate having a thickness of 3 mm using a bar coater (IMC-700 manufactured by Imoto Manufacturing Co., Ltd.) to form a coating film, and after evaporating the solvent from this coating film, the coating film was cured by irradiating it with ultraviolet light using a high-pressure mercury lamp to prepare an electromagnetic wave absorbing transparent substrate provided with an electromagnetic wave absorbing layer.
[0233] When the optical properties of the electromagnetic wave absorbing transparent substrate of Example 27 were measured in the same manner as in Example 14, VLT=72.2%, ST=37.0%, L * =88.6, a * =-3.8, b * =4.3. [Example 28] The dispersion liquid C prepared in Example 16 was used to remove the MIBK solvent in a vacuum dryer to obtain an electromagnetic wave absorbing particle dispersion powder C. 100 parts by mass of polycarbonate resin pellets and 0.15 parts by mass of dispersion powder C were uniformly mixed, and then melt-kneaded at 290°C using a twin-screw extruder (manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the extruded strands with a diameter of 3 mm were cut and pelletized to obtain a master batch C. The polycarbonate resin pellets and master batch C were blended so that the VLT would be about 72% when molded into a polycarbonate sheet with a thickness of 2 mm, and after uniformly mixing to obtain a mixture, the mixture was molded into a sheet with a size of 10 cm x 5 cm and a thickness of 2.0 mm using an injection molding machine to prepare an electromagnetic wave absorbing particle dispersion according to Example 28. The optical properties of the electromagnetic wave absorbing particle dispersion according to Example 28 were measured in the same manner as in Example 14, and the results were VLT = 72.4%, ST = 39.1%, L * =88.3, a * =-4.4,b * =4.6. [Example 29] The dispersion powder C prepared in Example 28 was mixed with a plasticizer, which is a compound of a monohydric alcohol and an organic acid ester, to prepare a plasticizer dispersion. The plasticizer dispersion and a polyvinyl acetal resin were blended and mixed in a ratio such that the VLT of the electromagnetic wave absorbing laminate according to Example 29 was about 72%, to prepare a resin composition, which was then loaded into a twin-screw extruder. The resin composition was then kneaded at 200°C, extruded from a T-die, and a 0.7 mm-thick intermediate film, which is an electromagnetic wave absorbing particle dispersion, was obtained by a calendar roll method. The obtained intermediate film was sandwiched and laminated between two soda lime glass substrates to produce an electromagnetic wave absorbing laminate according to Example 29. The optical properties of the electromagnetic wave absorbing laminate according to Example 29 were measured in the same manner as in Example 14, and the results were VLT=72.3%, ST=36.7%, L * =88.7, a * =-4.2, b * =4.1.
[0234] [Table 1]
[0235] [Table 2] The electromagnetic wave absorbing particle dispersion, the electromagnetic wave absorbing laminate, and the electromagnetic wave absorbing transparent substrate have been described above with reference to the embodiments and examples, but the present invention is not limited to the above embodiments and examples. Various modifications and changes are possible within the scope of the gist of the present invention described in the claims.
[0236] This application claims priority based on Japanese Patent Application No. 2020-015746, filed with the Japan Patent Office on January 31, 2020, the entire contents of which are incorporated herein by reference.
Claims
1. General formula Cs x W 1-y O 3-z (0.2≦x≦0.4, 0<y≦0.4, 0<z≦0.46), and including cesium tungsten oxide having an orthorhombic or hexagonal crystal structure; and a solid medium; An electromagnetic wave absorbing particle dispersion in which the electromagnetic wave absorbing particles are dispersed in the solid medium.
2. 2. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein the cesium tungsten oxide has linear or planar defects in one or more faces selected from the (010) face of an orthorhombic crystal, the {100} face which is a prism face of a hexagonal crystal, and the (001) face which is a base face of a hexagonal crystal.
3. 3. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein the cesium tungsten oxide has defects, the defects including tungsten vacancies.
4. 4. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein a part of O of the W-O octahedron constituting the orthorhombic or hexagonal crystal of the cesium tungsten oxide is randomly missing.
5. 5. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein the cesium tungsten oxide has a c-axis length in hexagonal crystal equivalent of 7.560 Å or more and 7.750 Å or less.
6. 6. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein a part of Cs in the cesium tungsten oxide is replaced by an additive element, and the additive element is one or more selected from the group consisting of Na, Tl, In, Li, Be, Mg, Ca, Sr, Ba, Al, and Ga.
7. 7. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein the average particle size of the electromagnetic wave absorbing particles is 0.1 nm or more and 200 nm or less.
8. 8. The electromagnetic wave absorbing particle dispersion according to claim 1, wherein the surfaces of the electromagnetic wave absorbing particles are modified with a compound containing one or more types of atoms selected from the group consisting of Si, Ti, Zr and Al.
9. The electromagnetic wave absorbing particle dispersion according to claim 1 , wherein the solid medium is a resin.
10. 10. The electromagnetic wave absorbing particle dispersion according to claim 9, wherein the resin is one type of resin selected from the group consisting of polyester resin, polycarbonate resin, acrylic resin, styrene resin, polyamide resin, polyethylene resin, vinyl chloride resin, olefin resin, epoxy resin, polyimide resin, fluororesin, ethylene-vinyl acetate copolymer, polyvinyl acetal resin, and ultraviolet curing resin, or a mixture of two or more types of resins selected from the group.
11. The electromagnetic wave absorbing particle dispersion according to claim 1 , which has a sheet, board or film shape.
12. 12. An electromagnetic-wave absorbing laminate having a laminated structure comprising the electromagnetic-wave absorbing particle dispersion according to claim 1 and a transparent substrate.
13. A transparent substrate; An electromagnetic wave absorbing layer is provided on at least one surface of the transparent substrate, 12. An electromagnetic-wave absorbing transparent substrate, wherein the electromagnetic-wave absorbing layer is the electromagnetic-wave absorbing particle dispersion according to claim 1.
14. A method for producing an electromagnetic wave absorbing particle dispersion according to any one of claims 1 to 11, comprising the steps of: The electromagnetic wave absorbing particles include cesium tungsten oxide precursor nCs 2 O.m.W.O. 3 A method for producing an electromagnetic wave absorbing particle dispersion using particles obtained by heating and reducing a crystal powder of (n, m are integers, 3.6≦m / n≦9.0) at 650° C. or higher and 950° C. or lower in a reducing gas atmosphere.
15. The electromagnetic wave absorbing particles have a main phase of Cs 4 W 11 O 35 15. The method for producing an electromagnetic wave absorbing particle dispersion according to claim 14, wherein the particles are obtained by heating and reducing the cesium tungsten oxide precursor containing the tungsten oxide phase at 650° C. or higher and 950° C. or lower in an atmosphere of a reducing gas.
Citation Information
Patent Citations
Sheet for heat insulation
JP1997107815A
Light shielding film
JP2003029314A
Composite tungsten oxide fine particle for forming solar radiation shielding body, method for producing the same, composite tungsten oxide fine particle dispersion liquid for forming solar radiation shielding body, and solar radiation shielding body
JP2013173642A
Infrared shielding material microparticle dispersion, infrared shield, process for producing infrared shielding material microparticle, and infrared shielding material microparticle
WO2005037932A1
Electromagnetic wave-absorbing transparent substrate
WO2019031246A1
Cited By
Near-infrared curable ink composition, near-infrared cured film, and method for producing near-infrared cured product
JP2023151573A
